Electrode active material layer for lithium-ion secondary batteries
Patent Information
- Application Number
- JP2025058018
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0030】 本発明によれば、結着剤、増粘剤、分散剤等の含有量を低減しても、プレス充填性(圧縮密度)及び電極強度に優れ、寿命特性(充放電サイクル特性)を改善することができる電極活物質層を提供することができる。
Smart Images

Figure 2026165570000002 
Figure 2026165570000003 
Figure 2026165570000004
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to an electrode active material layer for lithium-ion secondary batteries. BACKGROUND ART
[0002] The lithium-ion battery (LIB) business has achieved dramatic growth through continuous technological development aimed at downsizing, weight reduction, and enhanced functionality (pursuit of convenience) of portable devices, by leveraging its advantages such as high energy density, high voltage, and inherent safety performance. Now that global environmental issues and resource issues are gaining widespread attention, policies such as the promotion of eco-friendly vehicle adoption and the shift to renewable energy are expected to continue driving the growth of the lithium-ion battery market in the future. If lithium-ion batteries are applied as projected to privately owned electric vehicles (EVs) and stationary energy storage systems (for purposes such as renewable energy leveling), it is calculated that the demand for lithium-ion batteries by 2030 will be approximately 10 times that of 2018. This may lead to unfavorable situations for users from an economic perspective, such as sharp rises in battery costs due to resource shortages and the like. Therefore, research and development on reuse from the perspective of extending the service life of a single battery, or recycling from the perspective of resource recovery, has become active, and extending the service life of batteries is also effective from the standpoint of life cycle assessment (LCA).
[0003] Furthermore, new proposals are being made regarding the future of mobility, including EVs. Concepts such as CASE and MaaS, aimed at improving user convenience, are becoming a reality, and there are signs that mobility, including EVs, will shift from individual ownership to sharing in the future. In this trend, AIEVs (Artificial Intelligence Electric Vehicles), which are expected to be deployed in the market in the future, are EVs equipped with AI, with automated driving, vehicle sharing, and the vehicles being managed by a management company rather than being individually owned. The management company will provide mobility services (CASE) and various services needed by the user inside the vehicle (MaaS). In addition, since the management company will be able to control driving and charging / discharging, it will be possible to operate the vehicle with consideration for battery life and safety. Moreover, vehicle sharing can reduce the burden on users to about 1 / 5 of that compared to individual ownership, making it economically superior. In other words, in the future, replacing private cars, which are predominantly gasoline-powered, with AIEVs (shared cars) is expected to contribute to the global environment, reduce traffic accidents and congestion, provide a new mode of transportation for aging and depopulated areas, reduce individual costs, and enable more effective use of travel time. Furthermore, AIEVs can also function as a massive energy storage system, automatically charging and discharging electricity generated from renewable energy sources with significant fluctuations, using a management system operated by the management company.
[0004] However, achieving this would require a reassessment of the development direction of lithium-ion batteries, which are currently the mainstream (Figure 1).
[0005] In particular, a dramatic increase in the lifespan of batteries used in electric vehicles is absolutely essential. To realize AIEVs, unlike when a vehicle is privately owned, the total driving range of the vehicle needs to be, for example, 500,000 km or more. If the battery life remains at the current level, multiple battery replacements will be necessary, which will impair economic efficiency and will not solve resource problems. The required battery performance will prioritize lifespan over the currently mainstream requirements of energy density (driving range) and fast charging. Specifically, an energy density of 400 Wh / L per cell is required, and the vehicle driving range is 200-300 km with a 20-30 kWh battery, but the target for actual operating lifespan needs to be more than five times that of the current battery.
[0006] While various studies have been conducted to extend the lifespan of batteries, if the goal is to achieve a practical operating life that is more than five times longer than the current lifespan, a new perspective is needed. In contrast to the many degradation factors that have been studied in the past, such as degradation due to oxidation and reduction of active materials and components, degradation due to the insertion and removal of lithium ions from the active material, consumption of lithium ions due to the decomposition of the electrolyte, and degradation due to electrode loosening, the inventors of this invention have focused on the overvoltage factor.
[0007] The inventors have explained phenomena such as low-temperature degradation and secondary degradation by defining a new degradation mechanism called "degradation due to overvoltage factor (current × resistance)." Degradation due to overvoltage factor is defined as a degradation factor affected by load current and battery resistance (DC resistance). For example, degradation during low-temperature cycles can be explained as being caused by an increase in resistance at low temperatures, and degradation due to rapid charging can be explained as being caused by an increase in load current. Furthermore, as a battery degrades, its resistance increases, and as its capacity degrades, the load on the active material (apparent load) increases when the same current as the initial load is applied. Moreover, if gas accumulates in the electrode group, since gas does not allow ions to pass through, a load is placed on the electrode parts and active material other than the gas reservoir. From this perspective, one factor affecting battery life as an overvoltage factor is the uneven distribution of reactions within the electrodes. If reactions do not occur uniformly within the electrodes, stress accumulates on some of the active materials used in the electrodes during long-term battery operation. For example, in the case of the negative electrode, this can lead to lithium ion consumption due to localized strong reduction, and in the worst case, induce lithium electrodeposition. In the case of the positive electrode, it can induce degradation of the positive electrode active material due to cracks, etc. As a result, after repeated charge-discharge cycles, a sharp decrease in capacity and a sharp increase in resistance (secondary degradation) almost always occur. By homogenizing the reactions in the electrodes and suppressing the uneven distribution of reactions within the battery, this secondary degradation (sharp decrease in capacity) can be suppressed, and the battery life can be dramatically extended. For this reason, homogenizing the reactions within the battery is important, but currently, there are very few efforts being made to homogenize the reactions within the battery.
[0008] To homogenize the reactions within the battery, it is crucial to create an electrode structure that allows for uniform ion movement within the electrodes. While methods such as increasing the electrode porosity or decreasing the electrode's apparent weight have been explored, these methods inevitably reduce energy density (distance traveled). Therefore, these methods alone have limitations in achieving the aforementioned 400 Wh / L level. Furthermore, eliminating factors that can inhibit ion movement within the electrodes—specifically, binders typically used to strengthen the electrodes, thickeners and dispersants used to stabilize the electrode slurry—is considered effective in homogenizing ion movement. However, reducing or eliminating these components significantly reduces electrode strength, making it unable to follow volume changes during charging and discharging. This leads to a lack of current collection paths and a decrease in lifespan characteristics. Additionally, electrode manufacturing becomes difficult due to peeling and cracking of the electrode layer during roll-to-roll transport, pressing, and slitting processes.
[0009] As a result of diligent research, the present inventors have found that by using electrode constituent materials such as binders that can inhibit ion movement within the electrode, either by including or excluding only a very small amount, and by using a very small amount of carbon nanotubes to collect current between active material particles and maintain the shape of the electrode, it is possible to achieve sufficient strength to maintain the shape of the electrode while not inhibiting lithium ion movement, thereby homogenizing the reaction within the battery and extending the battery life (see, for example, Patent Document 1). [Prior art documents] [Patent Documents]
[0010] [Patent Document 1] International Publication No. 2023 / 090443 [Overview of the project] [Problems that the invention aims to solve]
[0011] However, the role of the binder is to (1) ensure adhesion between electrode active materials and (2) ensure adhesion between electrode active materials and electrode current collectors. If the binder is eliminated to the extreme, electrode strength becomes a technical challenge. If the electrode strength is low, the electrode active materials expand and contract during charging and discharging, which can damage the electrode structure and reduce conductivity within the electrode, potentially degrading the battery's lifespan due to current collection degradation. Therefore, simply reducing the binder does not allow for both mitigating reaction unevenness and improving lifespan characteristics.
[0012] Furthermore, research conducted by the inventors revealed that while electrode active materials with smaller particle sizes are less prone to cracking and therefore have superior lifespan characteristics, they suffer from drawbacks in terms of press-fillability (compression density) and electrode strength.
[0013] The present invention aims to solve the above-mentioned problems and provides an electrode active material layer that exhibits excellent press-fillability (compression density) and electrode strength, and improves lifespan characteristics (charge-discharge cycle characteristics), even when the content of binders, thickeners, dispersants, etc., is reduced. [Means for solving the problem]
[0014] In view of the above problems, the inventors have diligently conducted research. As a result, they have found that when predetermined amounts of large-particle electrode active material and small-particle electrode active material are used, the small-particle electrode active material fills the spaces between the large-particle electrode active material, resulting in excellent press-fillability (compression density) and electrode strength, and improving the lifespan characteristics (charge-discharge cycle characteristics) even when compared to the case of small-particle electrode active material alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). The present invention was completed based on these findings and further research. That is, the present invention encompasses the following configuration.
[0015] Item 1. Contains at least an electrode active material and carbon nanotubes, The electrode active material comprises an electrode active material (1) with an average particle diameter of less than 8.0 μm and an electrode active material (2) with an average particle diameter of greater than 8.0 μm. Assuming the total amount of the electrode active material layer for the lithium-ion secondary battery is 100% by mass, The total carbon nanotube content is 0.01 to 1.4% by mass, and An electrode active material layer for a lithium-ion secondary battery, wherein, with the total amount of the electrode active material being 100% by mass, the content of electrode active material (1) is 1 to 45% by mass, and the content of electrode active material (2) is 55 to 99% by mass.
[0016] Item 2. The total amount of the electrode active material layer for the lithium-ion secondary battery is set to 100% by mass, The content of the electrode active material is 96.0 to 99.9% by mass. The content of conductive additives other than carbon nanotubes is 0 to 3.5% by mass. The electrode active material layer for a lithium-ion secondary battery according to item 1, wherein the content of the electrode constituent materials, excluding the electrode active material, the carbon nanotubes, and conductive additives other than the carbon nanotubes, is 0 to 2.0% by mass.
[0017] Item 3. Assuming the total amount of the electrode active material layer is 100% by mass, The content of the electrode active material is 96.0 to 99.9% by mass. The content of conductive additives other than carbon nanotubes is 0 to 3.5% by mass. It does not contain electrode constituent materials other than the electrode active material, the carbon nanotube, and the conductive additive other than the carbon nanotube, This is the positive electrode for lithium-ion secondary batteries. An electrode active material layer for lithium-ion secondary batteries as described in item 2.
[0018] Item 4. Assuming the total amount of the electrode active material layer is 100% by mass, The content of the electrode active material is 96.6 to 99.9% by mass. The content of electrode constituent materials other than the electrode active material and the carbon nanotubes is 0 to 2.0% by mass, and The negative electrode for lithium-ion secondary batteries, An electrode active material layer for lithium-ion secondary batteries as described in item 2.
[0019] Item 5. Assuming the total amount of the electrode active material layer is 100% by mass, The content of the electrode active material is 97.4 to 99.9% by mass. The content of electrode constituent materials other than the electrode active material and the carbon nanotubes is 0 to 1.2% by mass. An electrode active material layer for lithium-ion secondary batteries as described in item 2.
[0020] Item 6. The electrode active material layer for lithium-ion secondary batteries described in Item 5, which is a negative electrode active material layer for lithium-ion secondary batteries.
[0021] Item 7. An electrode active material layer for a lithium-ion secondary battery according to any one of items 1 to 6, wherein the electrode active material is a material capable of intercalating and releasing lithium ions.
[0022] Item 8. An electrode active material layer for a lithium-ion secondary battery, as described in any one of items 1 to 7, for use in a lithium-ion secondary battery used in an electric vehicle for car sharing.
[0023] Item 9. An electrode for a lithium-ion secondary battery, comprising an electrode current collector, an undercoat layer, and an electrode active material layer for a lithium-ion secondary battery as described in any one of items 1 to 8.
[0024] Item 10. The electrode for a lithium-ion secondary battery according to Item 9, wherein the undercoat layer contains at least a conductive additive and the undercoat layer constituent material excluding the conductive additive.
[0025] Item 11. The electrode for a lithium-ion secondary battery as described in Item 10, wherein the content of the conductive additive is 20 to 80% by mass, with the total amount of the undercoat layer being 100% by mass, and the content of the undercoat layer constituent materials excluding the conductive additive is 20 to 80% by mass.
[0026] Item 12. An electrode for a lithium-ion secondary battery according to any one of items 9 to 11, wherein the thickness of the undercoat layer is 0.1 to 10.0 μm.
[0027] Item 13. A lithium-ion secondary battery electrode as described in any one of items 9 to 12, for use in electric vehicles for car sharing.
[0028] Item 14. A lithium-ion secondary battery comprising electrodes for lithium-ion secondary batteries as described in any one of items 9 to 13.
[0029] Item 15. A lithium-ion secondary battery as described in Item 14, used in electric vehicles for car sharing. [Effects of the Invention]
[0030] According to the present invention, even when the content of binders, thickeners, dispersants, etc., is reduced, it is possible to provide an electrode active material layer that exhibits excellent press-fillability (compression density) and electrode strength, and improves lifespan characteristics (charge-discharge cycle characteristics). [Brief explanation of the drawing]
[0031] [Figure 1] This is a schematic diagram illustrating the direction of lithium-ion battery development, taking into account a world view in which the use and operation of automobiles will change significantly. [Figure 2] The results of the press resistance test for Test Example 1 are shown. [Figure 3] The results for the powder compression density in Test Example 2 are shown. [Modes for carrying out the invention]
[0032] In this specification, "contains" is a concept that encompasses all of the following: "contains," "consist essentially of," and "consist of."
[0033] Furthermore, in this specification, the notation "A~B" means "greater than or equal to A and less than or equal to B".
[0034] 1. Electrode active material layer for lithium-ion secondary batteries and electrodes for lithium-ion secondary batteries Generally, the active material layer in an electrode often contains a considerable amount of electrode constituent materials other than the active material, such as binders, thickeners, and dispersants. Since these electrode constituent materials other than the active material are impermeable to lithium ions, if a considerable amount of these materials is present, it inhibits the movement of lithium ions, making uniform charging and discharging impossible. When lithium ion movement is inhibited, the reaction concentrates in areas where the inhibition of lithium ion movement is less pronounced. As a result, in the case of the negative electrode, this induces lithium electrodeposition, and in the case of the positive electrode, it induces degradation of the positive electrode active material due to cracks, etc. Therefore, after repeated charging and discharging cycles, a rapid decrease in capacity and a rapid increase in resistance (secondary degradation) occur. On the other hand, simply reducing the amount of electrode constituent materials other than the active material does not maintain sufficient strength to preserve the shape of the electrode. Cracks occur due to pressing during electrode manufacturing, and expansion and contraction during charging and discharging break the electrode structure, leading to a decrease in current collection degradation such as reduced conductivity within the electrode, thus reducing the battery's lifespan characteristics. Therefore, simply reducing the amount of electrode constituent materials other than the electrode active material does not allow for both mitigating reaction unevenness and improving lifespan characteristics. In the case of the negative electrode, as described above, the electrode structure breaks down, and the battery's lifespan characteristics deteriorate due to current collection degradation such as a decrease in conductivity within the electrode. Similarly, in the case of the positive electrode, as described above, it induces current collection degradation such as a decrease in conductivity within the electrode. For these reasons, it has been common technical knowledge that it is not possible to significantly reduce the amount of electrode constituent materials other than the electrode active material.
[0035] On the other hand, by not including or using only a very small amount of electrode constituent materials such as binders that can inhibit the movement of ions within the electrode, and by using a very small amount of carbon nanotubes to collect current between active material particles and maintain the shape of the electrode, it is possible to achieve sufficient strength to maintain the shape of the electrode while not inhibiting the movement of lithium ions, thereby homogenizing the reaction within the battery and extending the battery life.
[0036] However, the role of the binder is to (1) ensure adhesion between electrode active materials and (2) ensure adhesion between electrode active materials and electrode current collectors. If the binder is eliminated to the extreme, electrode strength becomes a technical challenge. If the electrode strength is low, the electrode active materials expand and contract during charging and discharging, which can damage the electrode structure and reduce conductivity within the electrode, potentially degrading the battery's lifespan due to current collection degradation. Therefore, simply reducing the binder does not allow for both mitigating reaction unevenness and improving lifespan characteristics.
[0037] Furthermore, research conducted by the inventors revealed that while electrode active materials with smaller particle sizes are less prone to cracking and therefore have superior lifespan characteristics, they suffer from drawbacks in terms of press-fillability (compression density) and electrode strength.
[0038] In contrast, the electrode active material layer for lithium-ion secondary batteries of the present invention contains at least an electrode active material and carbon nanotubes, wherein the electrode active material contains an electrode active material (1) with an average particle diameter of less than 8.0 μm and an electrode active material (2) with an average particle diameter greater than 8.0 μm, and the total amount of the electrode active material layer for lithium-ion secondary batteries is 100% by mass, the total content of carbon nanotubes is 0.01 to 1.4% by mass, and the total amount of the electrode active material is 100% by mass, the content of the electrode active material (1) is 1 to 45% by mass, and the content of the electrode active material (2) is 55 to 99% by mass.
[0039] By adopting this configuration, small-particle electrode active material is filled between large-particle electrode active material, resulting in excellent press-fillability (compression density) and electrode strength, as well as superior lifespan characteristics (charge-discharge cycle characteristics). Compared to the case where small-particle electrode active material is used alone, the lifespan characteristics (charge-discharge cycle characteristics) can be improved.
[0040] (1-1) Electrode active material layer The following describes four preferred embodiments of the electrode active material layer in order.
[0041] [1-1-1] Electrode active material layer for lithium-ion secondary battery (first embodiment) The electrode active material layer for a lithium-ion secondary battery according to the first aspect of the present invention is an electrode active material layer for a lithium-ion secondary battery containing an electrode active material and carbon nanotubes, wherein the content of the electrode active material is 97.4 to 99.9% by mass, the content of the carbon nanotubes is 0.01 to 1.4% by mass, and the content of electrode constituent materials other than the electrode active material and carbon nanotubes is 0 to 1.2% by mass, and it is preferably a negative electrode active material layer for a lithium-ion secondary battery. Furthermore, with the total amount of the electrode active material layer for a lithium-ion secondary battery being 100% by mass, the total content of carbon nanotubes is 0.01 to 1.4% by mass, and with the total amount of the electrode active material being 100% by mass, the content of the electrode active material (1) is 1 to 45% by mass, and the content of the electrode active material (2) is 55 to 99% by mass. In the electrode active material layer for lithium-ion secondary batteries according to the first embodiment, the total amount of electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than electrode active material (negative electrode active material) and carbon nanotubes (total amount of electrode active material layer for lithium-ion secondary batteries) is 100% by mass.
[0042] 1-1-1-1. Electrode active material The electrode active material (negative electrode active material) is not particularly limited; any material that can be used as an electrode active material (negative electrode active material) in a lithium-ion secondary battery, that is, a material capable of intercalating and releasing lithium ions, can be used. However, carbon materials such as natural graphite, artificial graphite, and amorphous carbon; metallic materials that can be alloyed with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Si alloys, Sn alloys, Al alloys, etc.; SiO x (0 <x<2)、SnO x(0<x<2), Si, Li₂TiO₃, vanadium oxides and the like, metal oxides capable of absorbing and releasing lithium ions; composite materials containing a metal material and a carbon material, such as a Si-C composite, a Sn-C composite, and the like. As the amorphous carbon, an amorphous carbon material described later can also be used. These electrode active materials (negative electrode active materials) may be used alone, or may be used in combination of two or more kinds. From the viewpoint of particularly suppressing the volume change of the electrode active material (negative electrode active material) during charge and discharge and easily particularly improving the charge-discharge cycle characteristics, materials containing no silicon, that is, carbon materials; metal materials containing no silicon such as Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Sn alloys, Al alloys and other metal materials capable of being alloyed with lithium; SnO x (0<x<2), Si, Li₂TiO₃, vanadium oxides and the like, metal oxides that do not contain silicon and are capable of absorbing and releasing lithium ions; composite materials that do not contain silicon and contain a metal material and a carbon material, such as a Sn-C composite, and the like can also be adopted. Among them, when a conductive material such as a carbon material is used as the electrode active material (negative electrode active material), the electrode active material (negative electrode active material) also functions as a conductive aid, and the content of substances that inhibit the movement of lithium ions can be particularly easily reduced.
[0043] As the electrode active material (negative electrode active material) as described above, from the viewpoint of particularly suppressing the volume change of the electrode active material (negative electrode active material) during charge and discharge, easily suppressing the capacity reduction due to the volume change, and easily particularly improving the charge-discharge cycle characteristics, the volume change of the electrode active material (negative electrode active material) during charge and discharge is 50% or less, preferably 20% or less. The smaller the volume change, the better, and no lower limit is set, but if a lower limit is to be set, it is 0%. The numerical value of this volume change is set to 0% when there is no volume change at all, and indicates how much the electrode active material (negative electrode active material) in a fully charged state is expanded compared with the electrode active material (negative electrode active material) in a fully discharged state, and is represented by the following formula: ((Volume at full charge) - (Volume at full discharge)) / (Volume at full discharge) × 100 is used for calculation.
[0044] Examples of electrode active materials (negative electrode active materials) that satisfy such volume changes include carbon materials such as natural graphite, artificial graphite, and amorphous carbon; and lithium composite titanium oxide (Li2TiO3, etc.). The volume changes of these materials vary depending on the material type and charge / discharge depth, but are around 10% for graphite and a few percent for amorphous carbon. Furthermore, when using multiple electrode active materials (negative electrode active materials), it is preferable that the average volume change of the electrode active materials (negative electrode active materials) falls within the above range.
[0045] There are no particular restrictions on the shape of the electrode active material (negative electrode active material), and various shapes such as spherical, flaky, lumpy, fibrous, whisker-like, and crushed can be used. Furthermore, a combination of electrode active materials (negative electrode active materials) of multiple shapes can be used. Note that "spherical" can refer to a perfect sphere, an elliptical shape, or other shapes.
[0046] As described above, in the present invention, small-particle electrode active material (negative electrode active material) is filled between large-particle electrode active material (negative electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and improving the lifespan characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material (negative electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). Specifically, the present invention contains electrode active material (negative electrode active material) (1) with an average particle diameter of less than 8.0 μm and electrode active material (negative electrode active material) (2) with an average particle diameter of 8.0 μm or more.
[0047] The average particle size of the electrode active material (negative electrode active material) (1), which is a small-particle electrode active material (negative electrode active material), is less than 8.0 μm, preferably 1.0 to 7.0 μm, and more preferably 2.0 to 6.0 μm. If the average particle size of the electrode active material (negative electrode active material) (1), which is a small-particle electrode active material (negative electrode active material), exceeds 8.0 μm, the electrode strength and life characteristics (charge-discharge cycle characteristics) will be inferior. The average particle size of the electrode active material (negative electrode active material) (1) is measured by laser diffraction-scattering.
[0048] On the other hand, the average particle size of the large-particle electrode active material (negative electrode active material) (2) is 8.0 μm or more, preferably 8.5 to 15.0 μm, and more preferably 9.0 to 13.0 μm. If the average particle size of the large-particle electrode active material (negative electrode active material) (2) is less than 8.0 μm, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) are inferior. The average particle size of the electrode active material (negative electrode active material) (2) is measured by laser diffraction-scattering.
[0049] The electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries according to the first embodiment can collect current between active material particles and maintain the shape of the electrodes using only a very small amount of carbon nanotubes. As a result, the amount of electrode constituent materials other than the electrode active material (negative electrode active material) can also be reduced. Consequently, it is easier to obtain sufficient strength to maintain the shape of the electrodes, and it is less likely to hinder the movement of lithium ions. Therefore, it can homogenize the reaction within the battery and extend the battery life. Compared to current electrode active material layers (negative electrode active material layers), it has a larger content of electrode active material (negative electrode active material). For this reason, the content of negative electrode active material is preferably 97.5 to 99.9% by mass, more preferably 97.8 to 99.7% by mass, and even more preferably 98.1 to 99.5% by mass. When using multiple electrode active materials (negative electrode active materials), it is preferable to adjust their total amount so that it falls within the above range. In the electrode active material layer for lithium-ion secondary batteries according to the first embodiment, the total amount of electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than electrode active material (negative electrode constituent materials) (total amount of electrode active material layer) is 100% by mass.
[0050] Furthermore, in the present invention, as described above, small-particle electrode active material (negative electrode active material) is filled between large-particle electrode active material (negative electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and improving lifespan characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material (negative electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). In this case, with the total amount of the electrode active material being 100% by mass, the content of electrode active material (1) is 1 to 45% by mass, and the content of electrode active material (2) is 55 to 99% by mass.
[0051] The content of the small-particle electrode active material (negative electrode active material) (1) is 1 to 45% by mass, preferably 10 to 44% by mass, more preferably 20 to 43% by mass, and even more preferably 30 to 42% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle diameter of the small-particle electrode active material (negative electrode active material) (1) is less than 1% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) will be inferior. Furthermore, if the average particle diameter of the small-particle electrode active material (negative electrode active material) (1) exceeds 45% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) will be inferior.
[0052] The content of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), is 55 to 99% by mass, preferably 56 to 90% by mass, more preferably 57 to 80% by mass, and even more preferably 58 to 70% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle diameter of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), is less than 55% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) are inferior. Also, if the average particle diameter of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), exceeds 99% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) are inferior.
[0053] 1-1-1-2. Carbon nanotubes The electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries according to the first embodiment facilitates current collection between active material particles and maintains electrode shape using a very small amount of carbon nanotubes, and also reduces the amount of electrode constituent materials other than the electrode active material (negative electrode active material). Because it does not easily hinder the movement of lithium ions, it can homogenize the reaction within the battery and extend the battery life. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it has excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics), and can improve life characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material alone. Although carbon nanotubes are also substances that hinder the movement of lithium ions, if used in small amounts, they do not hinder the movement of lithium ions, that is, they can maintain a homogenized reaction within the battery.
[0054] Carbon nanotubes are hollow carbon materials formed by the tubular closure of graphite sheets (i.e., carbon atom planes with a graphite structure or single-layer graphene sheets). Their diameter is on the nanometer scale, and their wall structure has a graphite structure. Carbon nanotubes with a wall structure of a single graphite sheet (single-layer graphene sheet) that are closed in a tubular shape are called single-walled carbon nanotubes. On the other hand, carbon nanotubes in which multiple graphite sheets are each closed in a tubular shape and nested together are called nested multi-walled carbon nanotubes. Such carbon nanotubes can be used individually or in combination of two or more types.
[0055] From the viewpoint of easily improving strength, easily increasing the number of carbon nanotubes per unit volume, reducing the carbon nanotube content required to maintain the electrode shape, and less inhibiting lithium ion movement, a small average outer diameter of carbon nanotubes is preferable. For this reason, the average outer diameter of carbon nanotubes is preferably 0.43 to 20 nm, and more preferably 0.43 to 10 nm. The average outer diameter of carbon nanotubes is measured by electron microscopy (TEM) observation. For carbon nanotubes having such an average outer diameter, the average inner diameter is set according to the average outer diameter.
[0056] While longer carbon nanotubes tend to have sufficient strength to maintain the electrode shape and facilitate current collection between negative electrode active materials, shorter average lengths are preferable from the viewpoint of improving dispersibility and minimizing interference with lithium ion movement. Therefore, the average length of carbon nanotubes is preferably 0.5 to 200 μm, and more preferably 1 to 50 μm. The average length of carbon nanotubes is measured by electron microscopy (SEM) observation.
[0057] The average aspect ratio of carbon nanotubes, defined as the ratio of the average length to the average outer diameter of the carbon nanotubes mentioned above, is preferably 25 to 200,000, and more preferably 100 to 50,000, from the viewpoint that a higher ratio makes it easier to maintain the shape of the electrode with a smaller carbon nanotube content, facilitates current collection between negative electrode active materials, and is less likely to hinder the movement of lithium ions, thus making it easier to homogenize the reaction within the battery and extend the battery life.
[0058] In this invention, carbon nanotubes can be used individually or as bundles of multiple carbon nanotubes, which tend to exhibit greater strength as a bundle. In either case, a very small amount of carbon nanotubes can be used to collect current between active material particles and maintain the shape of the electrodes. As a result, the amount of electrode constituent materials other than the electrode active material (negative electrode active material) can also be reduced. Consequently, the electrode has sufficient strength to maintain its shape and does not hinder the movement of lithium ions, thus homogenizing the reaction within the battery and extending the battery's lifespan.
[0059] Furthermore, having few defects in the graphene structure of carbon nanotubes, that is, having a high G / D ratio in the Raman spectrum, is considered desirable from the viewpoint of easily suppressing the reactivity between carbon nanotubes and the electrolyte. For this reason, in the present invention, the carbon nanotubes preferably have a G / D ratio of 1 to 200 in the Raman spectrum, and more preferably 50 to 150.
[0060] The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the first aspect of the present invention facilitates current collection between active material particles and maintenance of electrode shape using only a very small amount of carbon nanotubes, and also facilitates the reduction of the amount of negative electrode constituent materials other than the electrode active material (negative electrode active material). As a result, it is easy to obtain sufficient strength to maintain the shape of the electrode and is less likely to inhibit the movement of lithium ions, thus homogenizing the reaction within the battery and extending the battery life. Therefore, the carbon nanotube content is small. For this reason, in the electrode active material layer for lithium-ion secondary batteries according to the first aspect of the present invention, the carbon nanotube content is preferably 0.01 to 1.4 mass%, more preferably 0.1 to 1.1 mass%, and even more preferably 0.2 to 0.9 mass%. Although carbon nanotubes are substances that inhibit the movement of lithium ions, if the content is around 1.4 mass% or less, it is easy to obtain sufficient strength to maintain the shape of the electrode while keeping the reaction within the battery homogenous. Furthermore, when using multiple carbon nanotubes, it is preferable to adjust their total amount so that it falls within the above range. In addition, in the electrode active material layer for lithium-ion secondary batteries according to the first aspect of the present invention, the total amount of electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than electrode active material (negative electrode constituent materials) (total amount of composition) is 100% by mass.
[0061] 1-1-1-3. Electrode constituent materials other than electrode active materials and carbon nanotubes The electrode active material layer for lithium-ion secondary batteries according to the first aspect of the present invention facilitates current collection between active material particles and maintenance of electrode shape due to the very small amount of carbon nanotubes mentioned above, and also reduces the amount of electrode constituent materials other than the electrode active material (negative electrode active material). As a result, it is easier to maintain sufficient strength to maintain the shape of the electrode and is less likely to hinder the movement of lithium ions, thus enabling uniform reactions within the battery. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it has excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics), and can improve life characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material alone.
[0062] In this invention, the term "electrode active material (negative electrode active material)" and "electrode constituent materials other than carbon nanotubes (negative electrode constituent materials)" is a general term encompassing substances that have adhesive properties with the electrode active material (negative electrode active material) and electrode current collector (negative electrode current collector) (binding agents), as well as conductive additives other than carbon nanotubes such as carbon black, and dispersants, etc., which inhibit the movement of lithium ions other than carbon nanotubes (lithium ion movement inhibiting substances).
[0063] Examples of electrode components (negative electrode components) other than the electrode active material (negative electrode active material) and carbon nanotubes in this invention include, as conductive additives, acetylene black, Ketjen black, carbon black, graphene, amorphous carbon obtained by heat treatment of organic matter, etc., and as binders, thickeners, or dispersants, fluorinated polymers (polyvinylidene fluoride resin, polytetrafluoroethylene resin, vinylidene fluoride-hexafluoropropylene copolymer, etc.), polyolefin resins (styrene-butadiene copolymer resin, ethylene vinyl alcohol copolymer resin, etc.), synthetic rubbers (styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene propylene diene rubber, etc.), polyacrylonitrile, polyamide, polyimide, polyacrylic acid, polyacrylic acid ester, polyvinyl ether, carboxymethylcellulose, carboxymethylcellulose sodium salt, carboxymethylcellulose ammonium, polyurethane, hydroxypropylcellulose, hydroxyethylcellulose, methylcellulose, etc. Amorphous carbon materials described later can also be used as amorphous carbon. These electrode active materials (negative electrode active materials) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials) can be used individually or in combination of two or more types.
[0064] The electrode active material layer for lithium-ion secondary batteries according to the first aspect of the present invention facilitates current collection between active material particles and maintenance of electrode shape using a very small amount of carbon nanotubes, and also facilitates the reduction of the amount of electrode constituent materials other than the electrode active material (negative electrode active material). As a result, it is easier to achieve sufficient strength to maintain the shape of the electrode and is less likely to hinder the movement of lithium ions, thus enabling uniform reactions within the battery. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it is preferable that it has excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics). Therefore, it is preferable that the electrode constituent materials other than the electrode active material (negative electrode active material) and carbon nanotubes are either not included or, if included, in small amounts. Therefore, in the electrode active material layer for lithium-ion secondary batteries according to the first aspect of the present invention, the content of electrode active material (negative electrode active material) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials) is preferably 0 to 1.2% by mass, more preferably 0.2 to 1.1% by mass, and even more preferably 0.4 to 1.0% by mass. When using multiple electrode active materials (negative electrode active material) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials), it is preferable to adjust the total amount so that it falls within the above range. Although electrode active material (negative electrode active material) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials) are substances that inhibit the movement of lithium ions, if the content is around 1.2% by mass or less, it is less likely to inhibit the movement of lithium ions and is likely to have sufficient strength to maintain the shape of the electrode while keeping the reaction within the battery uniform. In the negative electrode active material layer for lithium-ion secondary batteries according to the first embodiment, the total amount of electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than electrode active material (negative electrode constituent materials) (total amount of composition) is 100% by mass.
[0065] 1-1-1-4. Electrode Active Material Layer for Lithium-ion Secondary Batteries The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) of the present invention may contain the above-mentioned electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than the electrode active material (negative electrode active material) and carbon nanotubes (negative electrode constituent materials).
[0066] The thickness of the electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries of the present invention is not particularly limited. However, a thinner layer is preferable in terms of ensuring lithium ion penetration and electrical conductivity, thereby facilitating a more uniform reaction. On the other hand, since the present invention aims to improve battery life by reducing factors that inhibit lithium ion movement and thus uniformizing the battery reaction, it is also possible to increase the thickness for better energy density per electrode. For this reason, the thickness of the electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries of the present invention is preferably 1 to 300 μm, more preferably 10 to 150 μm, and even more preferably 50 to 100 μm.
[0067] [1-1-2] Electrode active material layer for lithium-ion secondary battery (second embodiment) An electrode active material layer for a lithium-ion secondary battery according to a second aspect of the present invention is an electrode active material layer for a lithium-ion secondary battery containing an electrode active material and carbon nanotubes, wherein the average particle size of the electrode active material is 0.1 to 13.0 μm and its content is 96.6 to 99.9% by mass, the carbon nanotube content is 0.01 to 1.4% by mass, and the content of electrode constituent materials other than the electrode active material and carbon nanotubes is 0 to 2.0% by mass, and is an electrode active material layer for a lithium-ion secondary battery. Furthermore, with the total amount of the electrode active material layer for a lithium-ion secondary battery being 100% by mass, the total carbon nanotube content is 0.01 to 1.4% by mass, and with the total amount of the electrode active material being 100% by mass, the content of the electrode active material (1) is 1 to 45% by mass, and the content of the electrode active material (2) is 55 to 99% by mass. In the electrode active material layer for lithium-ion secondary batteries according to the second aspect of the present invention, the total amount of electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than electrode active material (negative electrode constituent materials) (total amount of composition) is 100% by mass.
[0068] When the particle size of the electrode active material (negative electrode active material) is reduced, the number of interfaces between the electrode active material (negative electrode active material) particles increases, resulting in more points where structural collapse can occur. Therefore, conventionally, it was even more difficult to significantly reduce the amount of electrode constituent materials other than the electrode active material (negative electrode active material). In the second embodiment, by adopting the above-described configuration, even though the particle size of the electrode active material (negative electrode active material) is reduced, resulting in more interfaces between the electrode active material (negative electrode active material) particles and thus more points where structural collapse can occur, it is possible to significantly reduce the amount of electrode constituent materials other than the electrode active material (negative electrode constituent material) and still easily collect current between the electrode active material (negative electrode active material) particles and maintain the shape of the electrode using only a very small amount of carbon nanotubes, and it is easy to maintain sufficient strength to maintain the shape of the electrode. Furthermore, because the electrode active material (negative electrode active material) is made smaller in particle size, the reaction area is increased, resulting in a smaller lithium ion flux per unit area. This reduces the risk of lithium deposition, especially under high load conditions and long-term use. In addition, the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is significantly reduced, which significantly improves lifespan characteristics. Moreover, while the electrode active material (negative electrode active material) is made smaller in particle size overall, the smaller particle size electrode active material is filled between the larger particle size electrode active material, resulting in excellent press-fillability (compression density) and electrode strength, as well as excellent lifespan characteristics (charge-discharge cycle characteristics). Compared to the case of small particle size electrode active material alone, it is easier to improve lifespan characteristics (charge-discharge cycle characteristics). In other words, the electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the second embodiment can be used to reduce the uneven distribution of reactions in lithium-ion secondary batteries.
[0069] 1-1-2-1. Electrode active material The electrode active material (negative electrode active material) is not particularly limited, and materials that can be used as the electrode active material (negative electrode active material) in lithium ion secondary batteries, that is, materials capable of absorbing and releasing lithium ions can be used, including carbon materials such as natural graphite, artificial graphite, and amorphous carbon; metal materials capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Si alloys, Sn alloys, and Al alloys; SiO x (0<x<2), SnO x (0<x<2), metal oxides capable of absorbing and releasing lithium ions such as Si, Li2TiO3, and vanadium oxides; composite materials containing a metal material and a carbon material such as a Si-C composite and a Sn-C composite. As the amorphous carbon, an amorphous carbon material described later can also be used. These electrode active materials (negative electrode active materials) can be used alone or in combination of two or more. From the viewpoint of particularly suppressing the volume change of the electrode active material (negative electrode active material) during charge and discharge and easily improving the charge-discharge cycle characteristics, silicon-free materials, that is, carbon materials; silicon-free metal materials such as metal materials capable of alloying with lithium such as Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Sn alloys, and Al alloys; SnO x (0<x<2), metal oxides that do not contain silicon and can absorb and release lithium ions, such as Si, Li2TiO3, and vanadium oxides; composite materials that do not contain silicon and contain a metal material and a carbon material, such as a Sn-C composite, can also be employed. In particular, when a conductive material such as a carbon material is used as the electrode active material (negative electrode active material), the electrode active material (negative electrode active material) also functions as a conductive aid, making it particularly easy to reduce the content of substances that inhibit the movement of lithium ions.
[0070] As for the electrode active material (negative electrode active material) described above, from the viewpoint of particularly suppressing the volume change of the electrode active material (negative electrode active material) during charging and discharging, making it easier to suppress the decrease in capacity due to volume change, and particularly improving the charge-discharge cycle characteristics, it is preferable that the volume change of the electrode active material (negative electrode active material) during charging and discharging is 50% or less, preferably 20% or less. The smaller the volume change, the better, and no lower limit is set, but if a lower limit were set, it would be 0%. This volume change value is set to 0% when there is no volume change at all, and indicates the extent to which the electrode active material (negative electrode active material) expands when fully charged compared to when fully discharged, as shown by the following formula: ((Volume when fully charged) - (Volume when fully discharged)) / (Volume when fully discharged) × 100 It is calculated by [method].
[0071] Examples of electrode active materials (negative electrode active materials) that satisfy such volume changes include carbon materials such as natural graphite, artificial graphite, and amorphous carbon; and lithium composite titanium oxide (Li2TiO3, etc.). The volume changes of these materials vary depending on the material type and charge / discharge depth, but are around 10% for graphite and a few percent for amorphous carbon. Furthermore, when using multiple electrode active materials (negative electrode active materials), it is preferable that the average volume change of the electrode active materials (negative electrode active materials) falls within the above range.
[0072] There are no particular restrictions on the shape of the electrode active material (negative electrode active material), and various shapes such as spherical, flaky, lumpy, fibrous, whisker-like, and crushed can be used. Furthermore, a combination of electrode active materials (negative electrode active materials) of multiple shapes can be used. Note that "spherical" can refer to a perfect sphere, an elliptical shape, or other shapes.
[0073] As described above, in the present invention, small-particle electrode active material (negative electrode active material) is filled between large-particle electrode active material (negative electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and also improving the lifespan characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material (negative electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). Specifically, the present invention contains electrode active material (negative electrode active material) (1) with an average particle diameter of less than 8.0 μm and electrode active material (negative electrode active material) (2) with an average particle diameter of 8.0 to 13.0 μm.
[0074] The average particle size of the electrode active material (negative electrode active material) (1), which is a small-particle electrode active material (negative electrode active material), is less than 8.0 μm, preferably 1.0 to 7.0 μm, and more preferably 2.0 to 6.0 μm. If the average particle size of the electrode active material (negative electrode active material) (1), which is a small-particle electrode active material (negative electrode active material), exceeds 8.0 μm, the electrode strength and life characteristics (charge-discharge cycle characteristics) will be inferior. The average particle size of the electrode active material (negative electrode active material) (1) is measured by laser diffraction-scattering.
[0075] On the other hand, the average particle size of the large-particle electrode active material (negative electrode active material) (2) is 8.0 to 13.0 μm, preferably 8.5 to 12.5 μm, and more preferably 9.0 to 12.0 μm. If the average particle size of the large-particle electrode active material (negative electrode active material) (2) is less than 8.0 μm, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) are inferior. The average particle size of the electrode active material (negative electrode active material) (2) is measured by laser diffraction-scattering.
[0076] The electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries according to the second embodiment has a smaller particle size for the electrode active material (negative electrode active material), which increases the number of interfaces between the electrode active material (negative electrode active material) particles and thus increases the number of points where structural collapse may occur. However, even if the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is significantly reduced, a very small amount of carbon nanotubes facilitates current collection between the electrode active material (negative electrode active material) particles and maintains the shape of the electrode, resulting in a strength that can easily maintain the shape of the electrode (negative electrode). Furthermore, because the reaction area is increased by the smaller particle size of the electrode active material (negative electrode active material), the lithium ion flux per unit area is reduced, which reduces the risk of lithium deposition, especially under high load conditions and long-term use. In addition, because the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is significantly reduced, the lifespan characteristics are significantly improved. Moreover, it is easy to maintain sufficient strength to maintain the shape of the electrode while keeping the reaction within the battery uniform. Therefore, the electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries according to the second embodiment has a larger content of electrode active material (negative electrode active material) compared to the current electrode active material layer (negative electrode active material layer). For this reason, in the electrode active material layer for lithium-ion secondary batteries according to the second embodiment, the content of electrode active material (negative electrode active material) is 96.6 to 99.9% by mass, preferably 97.6 to 99.8% by mass, and more preferably 98.1 to 99.7% by mass. When using multiple electrode active materials (negative electrode active materials), it is preferable to adjust the total amount so that it falls within the above range. In the electrode active material layer for lithium-ion secondary batteries according to the second embodiment, the total amount of electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than electrode active material (negative electrode constituent materials) (total amount of composition) is 100% by mass.
[0077] Furthermore, in the present invention, as described above, small-particle electrode active material (negative electrode active material) is filled between large-particle electrode active material (negative electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and improving lifespan characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material (negative electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). In this case, with the total amount of the electrode active material being 100% by mass, the content of electrode active material (1) is 1 to 45% by mass, and the content of electrode active material (2) is 55 to 99% by mass.
[0078] The content of the small-particle electrode active material (negative electrode active material) (1) is 1 to 45% by mass, preferably 10 to 44% by mass, more preferably 20 to 43% by mass, and even more preferably 30 to 42% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle diameter of the small-particle electrode active material (negative electrode active material) (1) is less than 1% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) will be inferior. Furthermore, if the average particle diameter of the small-particle electrode active material (negative electrode active material) (1) exceeds 45% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) will be inferior.
[0079] The content of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), is 55 to 99% by mass, preferably 56 to 90% by mass, more preferably 57 to 80% by mass, and even more preferably 58 to 70% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle diameter of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), is less than 55% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) are inferior. Also, if the average particle diameter of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), exceeds 99% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) are inferior.
[0080] 1-1-2-2. Carbon nanotubes The electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries according to the second embodiment facilitates current collection between active material particles and maintenance of electrode shape due to the use of a very small amount of carbon nanotubes. As a result, the electrode active material (negative electrode active material) has a small particle size, which increases the number of interfaces between electrode active material (negative electrode active material) particles, thus increasing the number of points where structural collapse may occur. Nevertheless, it tends to have sufficient strength to maintain the shape of the electrode (negative electrode) even when the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is reduced. Furthermore, because the reaction area is increased by the small particle size of the electrode active material (negative electrode active material), the lithium ion flux per unit area is reduced, which in turn reduces the risk of lithium deposition, especially under high load conditions and long-term use. In addition, because the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is significantly reduced, the lifespan characteristics tend to be significantly improved. Furthermore, by filling the gaps between large-particle electrode active materials with small-particle electrode active materials, the material exhibits excellent press-fillability (compression density) and electrode strength, as well as superior lifespan characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active materials alone, the lifespan characteristics (charge-discharge cycle characteristics) can be improved. Although carbon nanotubes are also substances that inhibit lithium ion movement, in small amounts they do not inhibit lithium ion movement, meaning they tend to have enough strength to maintain the shape of the electrode (negative electrode) while keeping the reaction within the battery uniform.
[0081] The carbon nanotubes that can be used are the same as those described in 1-1-2-1 above.
[0082] The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the second aspect of the present invention facilitates current collection between electrode active material (negative electrode active material) particles and maintains the shape of the electrode due to the use of a very small amount of carbon nanotubes. As a result, the electrode active material (negative electrode active material) has a small particle size, which increases the number of interfaces between electrode active material (negative electrode active material) particles and thus increases the number of points where structural collapse may occur. Nevertheless, it is easy to maintain sufficient strength to maintain the shape of the electrode (negative electrode) even when the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is reduced, and the electrode active material (negative electrode active material) has a small particle size. Because the reaction area is increased, the lithium ion flux per unit area is reduced, and in particular, the risk of lithium deposition is reduced under high load conditions and long-term use. Furthermore, because the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is significantly reduced, the lifespan characteristics are significantly improved. In addition, because small-particle electrode active material is filled between large-particle electrode active material, it is easy to achieve excellent press-fillability (compression density) and electrode strength, as well as excellent lifespan characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easy to improve lifespan characteristics (charge-discharge cycle characteristics). For this reason, in the electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer for lithium-ion secondary batteries) according to the second embodiment, the carbon nanotube content is small. For this reason, in the electrode active material layer for lithium-ion secondary batteries according to the second embodiment, the carbon nanotube content is 0.01 to 1.4 mass%, preferably 0.1 to 1.1 mass%, and more preferably 0.2 to 0.9 mass%. Although carbon nanotubes are also substances that inhibit the movement of lithium ions, if their concentration is around 1.4% by mass or less, they do not significantly inhibit the movement of lithium ions, especially when combined with the small particle size of the electrode active material (negative electrode active material). Furthermore, despite the small particle size of the electrode active material (negative electrode active material), it is easy to maintain sufficient strength to keep the reaction within the battery uniform and maintain the shape of the electrode (negative electrode). In the electrode active material layer for lithium-ion secondary batteries according to the second embodiment, the total amount of the electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than the electrode active material (negative electrode constituent materials) (total amount of composition) is 100% by mass.
[0083] 1-1-2-3. Electrode constituent materials other than electrode active materials and carbon nanotubes The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the second embodiment makes it easier to collect current between active material particles and maintain the shape of the electrode by using a very small amount of carbon nanotubes. As a result, the electrode active material (negative electrode active material) has a small particle size, which increases the number of interfaces between electrode active material (negative electrode active material) particles and thus increases the number of points where structural collapse may occur. Nevertheless, it tends to have enough strength to maintain the shape of the electrode (negative electrode) even when the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is reduced, and the electrode active material (negative electrode active material) has a small particle size. Because the reaction area is increased, the lithium ion flux per unit area is reduced, which in turn reduces the risk of lithium deposition, especially under high load conditions and long-term use. Furthermore, the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is significantly reduced, and because small-particle electrode active material is filled between large-particle electrode active material, it is easy to achieve excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easy to improve life characteristics (charge-discharge cycle characteristics).
[0084] In this invention, the electrode constituent materials (negative electrode constituent materials) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials) can be the same as those described in 1-1-1-3 above.
[0085] The electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries according to the second embodiment facilitates current collection between active material particles and maintenance of electrode shape due to the use of a very small amount of carbon nanotubes. As a result, the electrode active material (negative electrode active material) has a small particle size, which increases the number of interfaces between electrode active material (negative electrode active material) particles, thus increasing the number of points where structural collapse may occur. Nevertheless, it tends to have sufficient strength to maintain the shape of the electrode (negative electrode) even when the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is reduced. Furthermore, because the electrode active material (negative electrode active material) has a small particle size, the reaction area is increased, so per unit area The lithium ion flux is reduced, and in particular, the risk of lithium deposition is lessened under high load conditions and long-term use. Furthermore, the amount of electrode constituent materials other than the electrode active material (negative electrode active material) is significantly reduced, and small-particle electrode active material is filled between large-particle electrode active material, resulting in excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics). For this reason, electrode constituent materials other than the electrode active material (negative electrode active material) and carbon nanotubes are either not included or are included in small amounts. Therefore, in the electrode active material layer for lithium-ion secondary batteries according to the second embodiment, the content of electrode active material (negative electrode active material) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials) is 0 to 2.0 mass%, preferably 0 to 1.2 mass%, and more preferably 0 to 1.0 mass%. When using multiple electrode active materials (negative electrode active material) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials), it is preferable to adjust the total amount so that it falls within the above range.Although the electrode active material (negative electrode active material) and electrode constituent materials other than carbon nanotubes (negative electrode constituent materials) are substances that inhibit the movement of lithium ions, if their amount is around 2.0% by mass or less, they do not inhibit the movement of lithium ions as much as the small particle size of the electrode active material (negative electrode active material). Furthermore, despite the small particle size of the electrode active material (negative electrode active material), it is easy to maintain sufficient strength to keep the reaction within the battery uniform and maintain the shape of the electrode (negative electrode). In the electrode active material layer for lithium-ion secondary batteries according to the second embodiment, the total amount of the electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than the electrode active material (negative electrode active material) (total amount of composition) is 100% by mass.
[0086] 1-1-2-4. Electrode Active Material Layer for Lithium-ion Secondary Batteries The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) of the present invention may contain the above-mentioned electrode active material (negative electrode active material), carbon nanotubes, and electrode constituent materials other than the electrode active material (negative electrode active material) and carbon nanotubes (negative electrode constituent materials).
[0087] The thickness of the electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries of the present invention is not particularly limited. However, a thinner layer is preferable in terms of ensuring lithium ion penetration and electrical conductivity, thereby facilitating a more uniform reaction. On the other hand, since the present invention aims to improve battery life by reducing factors that inhibit lithium ion movement and thus uniformizing the battery reaction, it is also possible to increase the thickness for better energy density per electrode. For this reason, the thickness of the electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries of the present invention is preferably 1 to 300 μm, more preferably 10 to 150 μm, and even more preferably 50 to 100 μm.
[0088] [1-1-3] Electrode active material layer for lithium-ion secondary battery (third aspect) The electrode active material layer for lithium-ion secondary batteries according to a third aspect of the present invention is an electrode active material layer for lithium-ion secondary batteries containing an electrode active material and carbon nanotubes, wherein the content of the electrode active material is 88.6 to 99.9% by mass, the content of carbon nanotubes is 0.01 to 1.4% by mass, and the content of conductive additives other than carbon nanotubes is 0 to 10.0% by mass, and it does not contain electrode constituent materials other than the electrode active material, carbon nanotubes and conductive additives other than carbon nanotubes, and is a composition for forming a positive electrode active material layer for lithium-ion secondary batteries. Furthermore, with the total amount of the electrode active material layer for lithium-ion secondary batteries being 100% by mass, the total content of carbon nanotubes is 0.01 to 1.4% by mass, and with the total amount of the electrode active material being 100% by mass, the content of the electrode active material (1) is 1 to 45% by mass, and the content of the electrode active material (2) is 55 to 99% by mass. In the third embodiment of the electrode active material layer for lithium-ion secondary batteries, the total amount of electrode active material (positive electrode active material), carbon nanotubes, and conductive additives other than electrode active material (positive electrode active material) and carbon nanotubes (total amount of electrode active material layer for lithium-ion secondary batteries) is 100% by mass.
[0089] By adopting this configuration, it is easier to maintain sufficient strength to preserve the shape of the electrode (positive electrode), and because the amount of lithium ion inhibiting material is reduced, it is easier to suppress the inhibition of lithium ion movement. As a result, it is easier to homogenize the battery reaction and extend the battery life. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it is easy to achieve excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics). In other words, the electrode active material layer for lithium-ion secondary batteries (positive electrode active material layer for lithium-ion secondary batteries) according to the third embodiment can be used to reduce the uneven distribution of reactions in lithium-ion secondary batteries.
[0090] 1-1-3-1. Electrode active material The electrode active material (positive electrode active material) is not particularly limited, and a material that can be used as an electrode active material (positive electrode active material) in a lithium ion secondary battery, that is, a material capable of occluding and releasing lithium ions can be used. Examples thereof include lithium transition metal composite oxides having an α-NaFeO₂ type crystal structure, lithium transition metal oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, sulfur and the like. Examples of the lithium transition metal composite oxide having an α-NaFeO₂ type crystal structure include Li[Li x1 Ni γ1 Mn β1 Co (1-x1-γ1-β1) O₂ (0≦x1<0.5, 0≦γ1≦1, 0≦β1≦1, 0≦γ1+β1≦1), Li[Li x2 Ni γ2 Co β2 Al (1-x2-γ2-β2) O₂ (0≦x2<0.5, 0≦γ2≦1, 0≦β2≦1, 0≦γ2+β2≦1) and the like. Examples of the lithium transition metal oxide having a spinel type crystal structure include Li x3 Mn₂O₄ (0.9≦x3<1.5), Li x4 Ni γ4 Mn (2-γ4) O₄ (0.9≦x4<1.5, 0≦γ4≦2) and the like. Examples of the polyanion compound include LiFePO₄, LiMnPO₄, LiNiPO₄, LiCoPO₄, Li₃V₂(PO₄)₃, Li₂MnSiO₄, Li₂CoPO₄F and the like. Examples of the chalcogen compound include titanium disulfide, molybdenum disulfide, molybdenum dioxide and the like. Part of the atoms or polyanions in these materials may be substituted with atoms or anion species composed of other elements. These electrode active materials (positive electrode active materials) may be used alone, or two or more types may be used in combination. Among these, as the above-mentioned electrode active material (positive electrode active material), the above-mentioned lithium transition metal composite oxide is preferable from the viewpoint of higher energy density, and the polyanion compound is preferable from the viewpoint of higher safety.
[0091] The particle form of the electrode active material (positive electrode active material) is not particularly limited, and various forms such as secondary particles and single particles can be used. The shape is also not particularly limited, and various forms such as spherical, flaky, lumpy, fibrous, whisker-like, and fragmented can be used. Furthermore, positive electrode active materials of multiple shapes can be used in combination. Note that "spherical" can refer to a perfect sphere, an elliptical shape, or other shapes.
[0092] As described above, in the present invention, small-particle electrode active material (positive electrode active material) is filled between large-particle electrode active material (positive electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and improving lifespan characteristics (charge-discharge cycle characteristics) even when compared to the case of small-particle electrode active material (positive electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). Specifically, the present invention contains electrode active material (positive electrode active material) (1) with an average particle diameter of less than 8.0 μm and electrode active material (positive electrode active material) (2) with an average particle diameter of 8.0 μm or more.
[0093] The average particle size of the electrode active material (positive electrode active material) (1), which is a small-particle electrode active material (positive electrode active material), is less than 8.0 μm, preferably 1.0 to 7.0 μm, and more preferably 2.0 to 6.0 μm. If the average particle size of the electrode active material (positive electrode active material) (1), which is a small-particle electrode active material (positive electrode active material), exceeds 8.0 μm, the electrode strength and life characteristics (charge-discharge cycle characteristics) will be inferior. The average particle size of the electrode active material (positive electrode active material) (1) is measured by laser diffraction-scattering.
[0094] On the other hand, the average particle diameter of the electrode active material (positive electrode active material) (2), which is a large-particle electrode active material (positive electrode active material), is 8.0 μm or more, preferably 8.5 to 15.0 μm, and more preferably 9.0 to 13.0 μm. If the average particle diameter of the electrode active material (positive electrode active material) (2), which is a large-particle electrode active material (positive electrode active material), is less than 8.0 μm, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) are inferior. The average particle diameter of the electrode active material (positive electrode active material) (2) is measured by laser diffraction-scattering.
[0095] The electrode active material layer (positive electrode active material layer) for lithium-ion secondary batteries according to the third embodiment facilitates current collection between active material particles and maintenance of the electrode (positive electrode) shape using a very small amount of carbon nanotubes. As a result, it does not contain electrode constituent materials (positive electrode constituent materials) other than conductive additives, thus reducing the amount of electrode constituent materials (positive electrode constituent materials) other than the electrode active material (positive electrode active material). Consequently, it is easier to maintain sufficient strength to preserve the shape of the electrode (positive electrode), and it is less likely to hinder the movement of lithium ions. This makes it easier to homogenize the reaction within the battery and extend the battery life. Therefore, it has a higher content of electrode active material (positive electrode active material) compared to current electrode active material layers (positive electrode active material layers). For this reason, the electrode active material (positive electrode active material) content in the electrode active material layer for lithium-ion secondary batteries according to the third embodiment is 96.0 to 99.9% by mass, preferably 97.0 to 99.8% by mass, and more preferably 98.1 to 99.7% by mass. Furthermore, when using multiple electrode active materials (positive electrode active materials), it is preferable to adjust their total amount so that it falls within the above range. In the positive electrode active material layer for lithium-ion secondary batteries according to the third embodiment, the total amount of electrode active material (positive electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes (total amount of composition) is 100% by mass.
[0096] Furthermore, in the present invention, as described above, small-particle electrode active material (positive electrode active material) is filled between large-particle electrode active material (positive electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and improving lifespan characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material (negative electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). In this case, with the total amount of the electrode active material being 100% by mass, the content of electrode active material (1) is 1 to 45% by mass, and the content of electrode active material (2) is 55 to 99% by mass.
[0097] The content of the small-particle electrode active material (negative electrode active material) (1) is 1 to 45% by mass, preferably 10 to 44% by mass, more preferably 20 to 43% by mass, and even more preferably 30 to 42% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle diameter of the small-particle electrode active material (negative electrode active material) (1) is less than 1% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) will be inferior. Furthermore, if the average particle diameter of the small-particle electrode active material (negative electrode active material) (1) exceeds 45% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) will be inferior.
[0098] The content of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), is 55 to 99% by mass, preferably 56 to 90% by mass, more preferably 57 to 80% by mass, and even more preferably 58 to 70% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle diameter of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), is less than 55% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) are inferior. Also, if the average particle diameter of electrode active material (negative electrode active material) (2), which is a large-particle electrode active material (negative electrode active material), exceeds 99% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) are inferior.
[0099] 1-1-3-2. Carbon nanotubes The electrode active material layer (positive electrode active material layer for lithium-ion secondary batteries) of the present invention facilitates current collection between active material particles and maintenance of the electrode (positive electrode) shape using a very small amount of carbon nanotubes. As a result, it does not contain electrode constituent materials (positive electrode constituent materials) other than conductive additives, thus reducing the amount of electrode constituent materials other than the electrode active material (positive electrode active material). Consequently, it is easier to maintain sufficient strength to preserve the shape of the electrode (positive electrode), it is less likely to hinder lithium ion movement, it is easier to homogenize the reaction within the battery, and it is easier to extend the battery life. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it has excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is possible to improve life characteristics (charge-discharge cycle characteristics). Although carbon nanotubes are a substance that inhibits the movement of lithium ions, in small amounts they do not inhibit the movement of lithium ions, meaning they tend to have enough strength to maintain the shape of the electrode (positive electrode) while keeping the reaction within the battery uniform.
[0100] The carbon nanotubes that can be used are the same as those described in 1-1-2-1 above.
[0101] The electrode active material layer (positive electrode active material layer) for lithium-ion secondary batteries according to the third embodiment facilitates current collection between electrode active material (positive electrode active material) particles and maintenance of the electrode (positive electrode) shape using a very small amount of carbon nanotubes. As a result, it does not contain electrode constituent materials (positive electrode constituent materials) other than conductive additives, and the amount of electrode constituent materials (positive electrode constituent materials) other than the electrode active material (positive electrode active material) can also be reduced. As a result, it is easy to obtain sufficient strength to maintain the shape of the electrode (positive electrode), and it is easy to hinder the movement of lithium ions. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it is easy to obtain excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easy to improve life characteristics (charge-discharge cycle characteristics), and therefore the carbon nanotube content is small. Therefore, in the electrode active material layer for lithium-ion secondary batteries according to the third embodiment, the carbon nanotube content is 0.01 to 1.4% by mass, preferably 0.1 to 1.1% by mass, and more preferably 0.2 to 0.9% by mass. Although carbon nanotubes are substances that inhibit the movement of lithium ions, if the content is around 1.4% by mass or less, they do not easily inhibit the movement of lithium ions and tend to have sufficient strength to maintain the shape of the electrode (positive electrode) while keeping the reaction within the battery uniform. In the electrode active material layer for lithium-ion secondary batteries according to the third embodiment, the total amount of the electrode active material (positive electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes (total amount of composition) is 100% by mass.
[0102] 1-1-3-3. Conductive additives other than carbon nanotubes The electrode active material layer (positive electrode active material layer for lithium-ion secondary batteries) according to the third embodiment facilitates current collection between electrode active materials (positive electrode active materials) and maintenance of the electrode (positive electrode) shape using a very small amount of carbon nanotubes. As a result, it does not contain electrode constituent materials (positive electrode constituent materials) other than conductive additives, and the amount of electrode constituent materials other than electrode active materials (positive electrode active materials) can also be reduced. As a result, it is easy to obtain sufficient strength to maintain the shape of the electrode (positive electrode), and it is easy to prevent the movement of lithium ions from being hindered. Furthermore, since small-particle electrode active materials are filled between large-particle electrode active materials, it is easy to obtain excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active materials alone, it is easy to improve life characteristics (charge-discharge cycle characteristics), making it easier to homogenize the reaction within the battery and extend the battery life.
[0103] However, in the electrode active material layer for lithium-ion secondary batteries (positive electrode active material layer for lithium-ion secondary batteries) according to the third embodiment, depending on the particle morphology, particle size, particle shape, and electronic conductivity of the electrode active material (positive electrode active material), it is also possible to include a certain amount of conductive additive in addition to a very small amount of carbon nanotubes, from the viewpoint of maintaining current collection between the particles of the electrode active material (positive electrode active material). For example, when using a lithium transition metal composite oxide, which has a particle morphology of secondary particles, as the electrode active material (positive electrode active material), it is preferable to include a certain amount of conductive additive in addition to carbon nanotubes.
[0104] Examples of conductive additives other than carbon nanotubes in the electrode active material layer (positive electrode active material layer for lithium-ion secondary batteries) according to this third embodiment include carbon black such as acetylene black, furnace black, and Ketjen black; flake graphite; graphene; and amorphous carbon obtained by heat treatment of organic matter. These conductive additives other than carbon nanotubes can be used alone or in combination of two or more. Among these, carbon black is preferred from the viewpoint of not hindering lithium ion movement, stabilizing the electrode active material layer and reducing weight variation, homogenizing the reaction within the battery, and extending the battery life.
[0105] In the electrode active material layer for lithium-ion secondary batteries according to the third embodiment, the content of conductive additives other than carbon nanotubes is 0 to 3.5% by mass, preferably 0.4 to 2.5% by mass, and more preferably 0.8 to 1.5% by mass, from the viewpoint of making it easier to homogenize the reaction within the battery and extend the battery life, as small-particle electrode active materials are filled between large-particle electrode active materials, thus making it easier to improve the life characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active materials alone. When multiple conductive additives other than carbon nanotubes are used, it is preferable to adjust the total amount so that it is within the above range. Furthermore, in the electrode active material layer for lithium-ion secondary batteries according to the third embodiment, the total amount of electrode active material (positive electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes (total amount of electrode active material layer) is 100% by mass.
[0106] 1-1-3-4. Electrode constituent materials excluding electrode active materials, carbon nanotubes, and conductive additives other than carbon nanotubes The electrode active material layer (positive electrode active material layer) for lithium-ion secondary batteries according to the third embodiment facilitates current collection between electrode active material (positive electrode active material) particles and maintenance of the electrode (positive electrode) shape using a very small amount of carbon nanotubes. As a result, it does not contain electrode constituent materials (positive electrode constituent materials) other than the electrode active material (positive electrode active material) and conductive additives, thus reducing the amount of electrode constituent materials (positive electrode constituent materials) other than the electrode active material (positive electrode active material). Consequently, it is easier to achieve sufficient strength to maintain the shape of the electrode (positive electrode), and it is less likely to hinder the movement of lithium ions. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it is easy to achieve excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics), making it easier to homogenize the reaction within the battery and extend the battery life.
[0107] Conventional electrode active material layers for lithium-ion secondary batteries (positive electrode active material layers for lithium-ion secondary batteries) typically contain, in addition to the electrode active material (positive electrode active material) and conductive additives, some substances that inhibit the movement of lithium ions (lithium ion movement inhibitors), such as substances that provide adhesion to the electrode active material (positive electrode active material) and electrode current collector (positive electrode current collector) (binding agents), as well as thickeners and dispersants.
[0108] In contrast, the electrode active material layer for lithium-ion secondary batteries (positive electrode active material layer for lithium-ion secondary batteries) according to the third embodiment makes it easier to collect current between electrode active material (positive electrode active material) particles and maintain the shape of the electrode (positive electrode) using a very small amount of carbon nanotubes. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it tends to have excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics), which makes it easier to homogenize the reaction within the battery and extend the battery life. As a result, as described above, it is possible to have a configuration that does not contain electrode constituent materials (positive electrode constituent materials) other than conductive additives.
[0109] Other electrode components (positive electrode components) that are not included in the electrode active material layer (positive electrode active material layer for lithium-ion secondary batteries) according to the third embodiment include, for example, fluorine-based polymers (polyvinylidene fluoride resin, polytetrafluoroethylene resin, vinylidene fluoride-hexafluoropropylene copolymer, etc.), polyolefin resins (styrene-butadiene copolymer resin, ethylene vinyl alcohol copolymer resin, etc.), synthetic rubbers (styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene propylene diene rubber, etc.), polyacrylonitrile, polyamide, polyimide, polyacrylic acid, polyacrylic acid ester, polyvinyl ether, carboxymethylcellulose, carboxymethylcellulose sodium salt, carboxymethylcellulose ammonium, polyurethane, hydroxypropylcellulose, hydroxyethylcellulose, methylcellulose, etc., as binders, thickeners, or dispersants.
[0110] 1-1-3-5. Electrode Active Material Layer for Lithium-ion Secondary Batteries The electrode active material layer for lithium-ion secondary batteries (positive electrode active material layer for lithium-ion secondary batteries) of the present invention may contain the above-mentioned electrode active material (positive electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes, and may not contain electrode constituent materials other than the electrode active material (positive electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes.
[0111] The thickness of the electrode active material layer (positive electrode active material layer for lithium-ion secondary batteries) of the present invention is not particularly limited. However, a thinner layer is preferable in that it ensures lithium ion penetration and electrical conductivity, making it easier to homogenize the reaction. On the other hand, since the present invention aims to improve battery life by reducing factors that inhibit lithium ion movement and homogenizing the battery reaction, it is also possible to increase the thickness in order to increase the energy density per electrode. For this reason, the thickness of the electrode active material layer (positive electrode active material layer for lithium-ion secondary batteries) of the present invention is preferably 1 to 300 μm, more preferably 10 to 150 μm, and even more preferably 50 to 100 μm.
[0112] [1-1-4] Electrode active material layer for lithium-ion secondary battery (fourth aspect) The electrode active material layer for a lithium-ion secondary battery according to the fourth embodiment is an electrode active material layer for a lithium-ion secondary battery containing an electrode active material and carbon nanotubes, wherein the electrode active material contains an amorphous carbon material, and the carbon nanotube content is 0.01 to 0.8 mass% when the total amount of the composition is 100 mass%, and is a negative electrode active material layer for a lithium-ion secondary battery. Furthermore, when the total amount of the electrode active material layer for a lithium-ion secondary battery is 100 mass%, the total carbon nanotube content is 0.01 to 1.4 mass%, and when the total amount of the electrode active material is 100 mass%, the content of the electrode active material (1) is 1 to 45 mass%, and the content of the electrode active material (2) is 55 to 99 mass%.
[0113] Amorphous carbon materials have low electronic conductivity compared to graphite materials, so in order to maintain uniform reactions within the battery, it is necessary to form uniform electron conduction paths. On the other hand, when using conductive additives with a small aspect ratio, such as carbon black, the amount of conductive additive required to form the above electron conduction paths becomes large, which may inhibit the movement of lithium ions. On the other hand, carbon nanotubes with a high aspect ratio can form uniform electron conduction paths in small amounts. Thus, by using amorphous carbon materials and carbon nanotubes in combination, it is possible to suppress the inhibition of lithium ion movement while forming uniform electron conduction paths, thereby making it easier to maintain uniform reactions within the battery. Furthermore, although carbon nanotubes are substances that can inhibit the movement of lithium ions, the carbon nanotube content in this invention is very small, making it easier to maintain uniform reactions within the battery, and the synergistic effect with amorphous carbon materials makes it easier to extend the battery's lifespan. Furthermore, while the electrode active material (negative electrode active material) is generally made smaller in particle size, the smaller particle size electrode active material is filled between the larger particle size electrode active material, resulting in excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small particle size electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics). In other words, the electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment can be used to reduce the uneven distribution of reactions in lithium-ion secondary batteries.
[0114] 1-1-4-1. Electrode active material As an amorphous carbon material used as an electrode active material (negative electrode active material), amorphous layered carbon materials are preferred from the viewpoint of easily homogenizing the reaction within the battery and extending the battery's lifespan.
[0115] The interlayer distance of the (002) plane of amorphous layered carbon material is preferably 0.35 nm or greater, and more preferably 0.36 nm or greater, from the viewpoint of facilitating homogenization of reactions within the battery and extending the battery life. There is no particular upper limit to the interlayer distance of the (002) plane of amorphous layered carbon material, but it is usually 0.40 nm. The interlayer distance of amorphous layered carbon material is measured by X-ray diffraction.
[0116] As described above, in the present invention, small-particle electrode active material (negative electrode active material) is filled between large-particle electrode active material (negative electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and improving the lifespan characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material (negative electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). Specifically, it contains amorphous layered carbon material (1) with an average particle diameter of less than 8.0 μm and amorphous layered carbon material (2) with an average particle diameter of 8.0 to 13.0 μm.
[0117] The average particle size of the amorphous layered carbon material (1), which is a small-particle electrode active material (negative electrode active material), is less than 8.0 μm, preferably 1.0 to 7.0 μm, and more preferably 2.0 to 6.0 μm. If the average particle size of the amorphous layered carbon material (1), which is a small-particle electrode active material (negative electrode active material), exceeds 8.0 μm, the electrode strength and lifetime characteristics (charge-discharge cycle characteristics) will be inferior. The average particle size of the amorphous layered carbon material (1) is measured by laser diffraction and scattering.
[0118] On the other hand, the average particle size of the amorphous layered carbon material (2), which is the large-particle electrode active material (negative electrode active material), is 8.0 to 13.0 μm, preferably 8.5 to 12.5 μm, and more preferably 9.0 to 12.0 μm. If the average particle size of the amorphous layered carbon material (2), which is the large-particle electrode active material (negative electrode active material), is less than 8.0 μm, the press-fillability (compression density), electrode strength, and lifetime characteristics (charge-discharge cycle characteristics) are inferior. The average particle size of the amorphous layered carbon material (2) is measured by laser diffraction / scattering.
[0119] Examples of amorphous carbon materials that satisfy the above conditions include hard carbon (carbon material that is difficult to graphitize), soft carbon (carbon material that is easily graphitized), and mesophase pitch carbide. These amorphous carbon materials can be used individually or in combination of two or more types. Among these, hard carbon is preferred from the viewpoint of easily homogenizing the reaction in the battery and extending the battery life. In this invention, hard carbon means an amorphous carbon material in which the interlayer distance of the (002) plane does not become less than 0.34 nm when fired at 3000°C. Soft carbon means an amorphous carbon material in which the interlayer distance of the (002) plane becomes less than 0.34 nm when fired at 3000°C.
[0120] There are no particular restrictions on the shape of the electrode active material (negative electrode active material), and various shapes such as spherical, flaky, lumpy, fibrous, whisker-like, and crushed can be used. Furthermore, a combination of electrode active materials (negative electrode active materials) of multiple shapes can be used. Note that "spherical" can refer to a perfect sphere, an elliptical shape, or other shapes.
[0121] The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment uses an amorphous carbon material as the electrode active material (negative electrode active material) and uses a very small amount of carbon nanotubes to suppress the inhibition of lithium ion movement, form a uniform electron conduction path, improve strength with single-walled carbon nanotubes, and stabilize the electrode active material layer by wrapping single-walled carbon nanotubes around multi-walled carbon nanotubes, thereby reducing weight variation. This makes it easier to homogenize the reaction within the battery and extend the battery life. In the present invention, the content of the electrode active material (negative electrode active material) is preferably 96.0 to 99.9% by mass, more preferably 97.0 to 99.8% by mass, and even more preferably 98.1 to 99.7% by mass. When using multiple electrode active materials (negative electrode active materials), it is preferable to adjust the total amount so that it falls within the above range. In the fourth embodiment of the electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer for lithium-ion secondary batteries), the total amount (total amount of composition) of the electrode active material (negative electrode active material), carbon nanotubes, conductive additives other than carbon nanotubes, and electrode constituent materials (negative electrode constituent materials) (other electrode constituent materials (negative electrode constituent materials)) excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes is 100% by mass.
[0122] Furthermore, in the present invention, as described above, small-particle electrode active material (negative electrode active material) is filled between large-particle electrode active material (negative electrode active material), resulting in excellent press-fillability (compression density) and electrode strength, and improving lifespan characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material (negative electrode active material) alone, which has excellent lifespan characteristics (charge-discharge cycle characteristics). In this case, with the total amount of the electrode active material being 100% by mass, the content of amorphous layered carbon material (1), which is small-particle electrode active material (negative electrode active material), is 1 to 45% by mass, and the content of amorphous layered carbon material (2), which is large-particle electrode active material (negative electrode active material), is 55 to 99% by mass.
[0123] The content of amorphous layered carbon material (1), which is a small-particle electrode active material (negative electrode active material), is 1 to 45% by mass, preferably 10 to 44% by mass, more preferably 20 to 43% by mass, and even more preferably 30 to 42% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle size of the amorphous layered carbon material (1), which is a small-particle electrode active material (negative electrode active material), is less than 1% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) will be inferior. Furthermore, if the average particle size of the amorphous layered carbon material (1), which is a small-particle electrode active material (negative electrode active material), exceeds 45% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) will be inferior.
[0124] The content of amorphous layered carbon material (2), which is the large-particle electrode active material (negative electrode active material), is 55 to 99% by mass, preferably 56 to 90% by mass, more preferably 57 to 80% by mass, and even more preferably 58 to 70% by mass, based on 100% by mass of the total amount of electrode active material. If the average particle diameter of the amorphous layered carbon material (2), which is the large-particle electrode active material (negative electrode active material), is less than 55% by mass, the press-fillability (compression density), electrode strength, and life characteristics (charge-discharge cycle characteristics) are inferior. Also, if the average particle diameter of the amorphous layered carbon material (2), which is the large-particle electrode active material (negative electrode active material), exceeds 99% by mass, the electrode strength and life characteristics (charge-discharge cycle characteristics) are inferior.
[0125] 1-1-4-2. Carbon nanotubes The electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries according to the fourth embodiment uses an amorphous carbon material as the electrode active material (negative electrode active material) and uses a very small amount of carbon nanotubes to suppress the inhibition of lithium ion movement and form a uniform electron conduction path. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it tends to have excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics), and it tends to improve life characteristics (charge-discharge cycle characteristics) compared to the case of small-particle electrode active material alone. Although carbon nanotubes are also a substance that inhibits lithium ion movement, in small amounts they do not inhibit lithium ion movement, that is, they tend to homogenize the reaction in the battery and tend to extend the battery life.
[0126] The carbon nanotubes that can be used are the same as those described in 1-1-2-1 above.
[0127] The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment uses an amorphous carbon material as the electrode active material (negative electrode active material) and uses a very small amount of carbon nanotubes. This suppresses the inhibition of lithium ion movement and forms a uniform electron conduction path. Furthermore, small-particle electrode active material is filled between large-particle electrode active material, resulting in excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics), thus making it easier to homogenize the reaction within the battery and extend the battery life. For this reason, the carbon nanotube content is small. In this invention, the carbon nanotube content is 0.01 to 0.8 mass%, preferably 0.02 to 0.7 mass%, and more preferably 0.05 to 0.6 mass%. Although carbon nanotubes are substances that inhibit the movement of lithium ions, if their concentration is around 0.8% by mass or less, they do not significantly inhibit the movement of lithium ions, making it easier to maintain a uniform reaction within the battery. In the fourth embodiment of the electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer for lithium-ion secondary batteries), the total amount (total amount of composition) of the electrode active material (negative electrode active material), carbon nanotubes, conductive additives other than carbon nanotubes, and electrode constituent materials (negative electrode constituent materials) (other electrode constituent materials (negative electrode constituent materials)) excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes is 100% by mass.
[0128] 1-1-4-3. Conductive additives other than carbon nanotubes The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment uses an amorphous carbon material as the electrode active material (negative electrode active material) and uses a very small amount of carbon nanotubes to suppress the obstruction of lithium ion movement and form a uniform electron conduction path. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it is easy to achieve excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easy to improve life characteristics (charge-discharge cycle characteristics), making it easier to homogenize the reaction within the battery and extend the battery life.
[0129] However, in the electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment, depending on the particle morphology, particle size, particle shape, and electronic conductivity of the amorphous carbon material, it is possible to include a certain amount of conductive additive in addition to a very small amount of carbon nanotubes, from the viewpoint of maintaining current collection between the particles of the electrode active material (negative electrode active material). For example, when using an amorphous carbon material with spherical particle shape as the electrode active material (negative electrode active material), it is preferable to include a certain amount of conductive additive in addition to carbon nanotubes.
[0130] Other conductive additives that can be used besides carbon nanotubes are the same as those described in 1-1-3-3 above.
[0131] In the present invention, when a conductive additive other than carbon nanotubes is included, the content of the conductive additive other than carbon nanotubes is preferably 0.1 to 3.5% by mass, more preferably 0.2 to 2.5% by mass, and even more preferably 0.3 to 1.5% by mass, from the viewpoint of easily homogenizing the reaction in the battery and easily extending the battery life. When multiple conductive additives other than carbon nanotubes are used, it is preferable to adjust the total amount so that it falls within the above range. In the electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment, the total amount (total amount of composition) of the electrode active material (negative electrode active material), carbon nanotubes, conductive additives other than carbon nanotubes, and electrode constituent materials (negative electrode constituent materials) (other electrode constituent materials (negative electrode constituent materials)) excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes is 100% by mass.
[0132] Furthermore, for similar reasons, with the total amount of carbon nanotubes and conductive additives other than carbon nanotubes being 100% by mass, the carbon nanotube content is preferably 0.1 to 100.0% by mass, more preferably 0.5 to 60% by mass, and even more preferably 1.0 to 45.0% by mass. When using multiple conductive additives other than carbon nanotubes, it is preferable to adjust their total amount so that it falls within the above range.
[0133] 1-1-4-4. Electrode constituent materials (other electrode constituent materials) excluding electrode active materials, carbon nanotubes, and conductive additives other than carbon nanotubes. The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment uses an amorphous carbon material as the electrode active material (negative electrode active material) and uses a very small amount of carbon nanotubes to suppress the obstruction of lithium ion movement and form a uniform electron conduction path. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it is easy to achieve excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easy to improve life characteristics (charge-discharge cycle characteristics), making it easier to homogenize the reaction within the battery and extend the battery life.
[0134] In this invention, the term "electrode constituent materials (negative electrode constituent materials)" (other electrode constituent materials (negative electrode constituent materials)), excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes, is a general term for substances that inhibit the movement of lithium ions (lithium ion movement inhibiting substances), excluding carbon nanotubes and conductive additives other than carbon nanotubes, such as substances that have adhesive properties with the electrode active material (negative electrode active material) and electrode current collectors (negative electrode current collectors) (binding agents), dispersants, etc.
[0135] The electrode components (negative electrode components) (other electrode components (negative electrode components)), excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes, can be the same as those described in 1-1-3-4 above. The electrode components (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes (negative electrode components) (other electrode components (negative electrode components)), excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes, can be used individually or in combination of two or more types.
[0136] The electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment uses an amorphous carbon material as the electrode active material (negative electrode active material) and uses a very small amount of carbon nanotubes to suppress the obstruction of lithium ion movement and form a uniform electron conduction path. Furthermore, since small-particle electrode active material is filled between large-particle electrode active material, it is easy to achieve excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easy to improve life characteristics (charge-discharge cycle characteristics), making it easier to homogenize the reaction within the battery and extend the battery life. From this viewpoint, it is preferable that the content of electrode constituent materials (negative electrode constituent materials) (other electrode constituent materials (negative electrode constituent materials)), excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes, be small. On the other hand, from the viewpoint of easily having strength sufficient to maintain the shape of the electrode, it is preferable that the content be above a certain level. Therefore, in the electrode active material layer (negative electrode active material layer for lithium-ion secondary batteries) according to the fourth embodiment, the content of electrode constituent materials (negative electrode constituent materials) (other electrode constituent materials (negative electrode constituent materials)), excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes, is preferably 0.1 to 10.0 mass%, more preferably 1.0 to 8.0 mass%, and even more preferably 2.0 to 6.0 mass%. When multiple electrode constituent materials (negative electrode constituent materials) (other electrode constituent materials (negative electrode constituent materials)), excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes, are used, it is preferable to adjust the total amount so that it falls within the above range. In the fourth embodiment of the electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer for lithium-ion secondary batteries), the total amount (total amount of composition) of the electrode active material (negative electrode active material), carbon nanotubes, conductive additives other than carbon nanotubes, and electrode constituent materials (negative electrode constituent materials) (other electrode constituent materials (negative electrode constituent materials)) excluding the electrode active material (negative electrode active material), carbon nanotubes, and conductive additives other than carbon nanotubes is 100% by mass.
[0137] 1-1-4-5. Electrode Active Material Layer for Lithium-ion Secondary Batteries The electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer for lithium-ion secondary batteries) of the present invention contains the above-mentioned electrode active material and carbon nanotubes, and may optionally contain conductive additives other than carbon nanotubes and electrode constituent materials (negative electrode constituent materials) other than the electrode active material (negative electrode active material), carbon nanotubes and conductive additives other than carbon nanotubes.
[0138] The thickness of the electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries of the present invention is not particularly limited. However, a thinner layer is preferable in terms of ensuring lithium ion penetration and electrical conductivity, thereby facilitating a more uniform reaction. On the other hand, since the present invention aims to improve battery life by reducing factors that inhibit lithium ion movement and thus uniformizing the battery reaction, it is also possible to increase the thickness for better energy density per electrode. For this reason, the thickness of the electrode active material layer (negative electrode active material layer) for lithium-ion secondary batteries of the present invention is preferably 1 to 300 μm, more preferably 10 to 150 μm, and even more preferably 50 to 100 μm.
[0139] (1-2) Electrode current collector The electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer and positive electrode active material layer for lithium-ion secondary batteries) described above can be formed on a lithium-ion secondary battery electrode current collector (negative electrode current collector and positive electrode current collector) to form an electrode for lithium-ion secondary batteries (negative electrode and positive electrode for lithium-ion secondary batteries).
[0140] The electrode current collectors (negative electrode current collector and positive electrode current collector) are not particularly limited, and current collectors commonly used in lithium-ion secondary batteries can be used.
[0141] The negative electrode current collector is preferably made of a material that is electrochemically stable at the potential used and has high electronic conductivity, such as copper, stainless steel, nickel, or carbon material. This negative electrode current collector can be in the form of a foil, mesh, or other similar component.
[0142] The positive electrode current collector is preferably made of a material that is electrochemically stable at the potential used and has high electronic conductivity, such as aluminum, stainless steel, or carbon material. This positive electrode current collector can be in the form of a foil, mesh, or other similar component.
[0143] (1-3) Undercoat layer The electrode active material layer for lithium-ion secondary batteries (negative electrode active material layer and positive electrode active material layer for lithium-ion secondary batteries) of the present invention described above can be formed directly on the electrode current collector for lithium-ion secondary batteries (negative electrode current collector and positive electrode current collector for lithium-ion secondary batteries), but it is preferable to form it on the electrode current collector for lithium-ion secondary batteries (negative electrode current collector and positive electrode current collector for lithium-ion secondary batteries) via an undercoat layer to form the electrode for lithium-ion secondary batteries (negative electrode and positive electrode for lithium-ion secondary batteries).
[0144] In the present invention, the undercoat layer, by being present between the electrode current collector and the electrode active material layer, does not hinder the movement of lithium ions even if the electrode constituent materials such as binders, thickeners, and dispersants in the electrode active material layer are absent or present in very small amounts. Furthermore, small-particle electrode active material is filled between large-particle electrode active material, resulting in excellent press-fillability (compression density) and electrode strength, as well as excellent life characteristics (charge-discharge cycle characteristics). Compared to the case of small-particle electrode active material alone, it is easier to improve life characteristics (charge-discharge cycle characteristics), thus making it easier to homogenize the reaction within the battery and extend the battery life. In addition, it improves the strength of the battery and prevents cracks from occurring even if high pressure is applied locally due to pressing during electrode manufacturing.
[0145] While the undercoat layer is not particularly limited, it is preferable that it contains at least a conductive additive and the undercoat layer constituent materials excluding the electrode active material and conductive additive, in order to improve the strength of the battery and to homogenize the reaction within the battery, even if the electrode constituent materials such as binders, thickeners, and dispersants in the electrode active material layer are absent or present in very small amounts.
[0146] [1-3-1] Conductive additive Examples of conductive additives include acetylene black, Ketjenblack, carbon black, carbon nanotubes, graphite, graphene, and amorphous carbon obtained by heat treatment of organic materials. Amorphous carbon materials, as described later, can also be used. These conductive additives can be used individually or in combination of two or more.
[0147] Furthermore, while there are no particular restrictions on the particle size of the conductive additive in the undercoat layer, even if the electrode constituent materials such as binders, thickeners, and dispersants in the electrode active material layer are absent or present in very small amounts, the movement of lithium ions is less likely to be inhibited. This makes it easier to homogenize the reaction within the battery, extend the battery life, improve the battery's strength, and prevent cracks from occurring due to pressing during electrode manufacturing even when high pressure is applied locally. Therefore, when the conductive additive is in particulate form, the average particle size is preferably 0.001 to 10 μm, more preferably 0.01 to 5 μm, and even more preferably 0.1 to 1 μm. The average particle size of the conductive additive is measured by laser diffraction / scattering.
[0148] In the lithium-ion secondary battery electrode (negative electrode or positive electrode for lithium-ion secondary battery) of the present invention, the content of the conductive additive in the undercoat layer is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and even more preferably 40 to 60% by mass, from the viewpoint of not inhibiting lithium ion movement even when electrode constituent materials such as binders, thickeners, and dispersants in the electrode active material layer are absent or present in very small amounts, thereby making it easier to homogenize the reaction within the battery, extending the battery life, improving the strength of the battery, making it less likely for cracks to occur due to pressing during electrode manufacturing even when high loads are applied locally, and making it less likely for the undercoat layer and the electrode active material layer to peel off. When multiple conductive additives are used, it is preferable to adjust their total amount so that it falls within the above range. In the undercoat layer, the total amount of the conductive additive and the undercoat layer constituent materials excluding the conductive additive (total amount of the undercoat layer) is 100% by mass.
[0149] [1-3-2] Undercoat layer constituent materials excluding conductive additives The undercoat layer constituent materials (negative electrode undercoat layer constituent materials or positive electrode undercoat layer constituent materials), excluding conductive additives, include substances that have adhesion to conductive additives and electrode current collectors (negative electrode current collector or positive electrode current collector) (binding agents), as well as thickeners, dispersants, and the like.
[0150] Examples of undercoat layer constituent materials (negative electrode undercoat layer constituent materials or positive electrode undercoat layer constituent materials) excluding such conductive additives include, for example, fluorine-based polymers (polyvinylidene fluoride resin, polytetrafluoroethylene resin, vinylidene fluoride-hexafluoropropylene copolymer, etc.), polyolefin resins (styrene-butadiene copolymer resin, ethylene vinyl alcohol copolymer resin, etc.), synthetic rubbers (styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene propylene diene rubber, etc.), polyacrylonitrile, polyamide, polyimide, polyacrylic acid, polyacrylic acid ester, polyvinyl ether, carboxymethylcellulose, carboxymethylcellulose sodium salt, carboxymethylcellulose ammonium, polyurethane, hydroxypropylcellulose, hydroxyethylcellulose, methylcellulose, etc., used as binders, thickeners, or dispersants.
[0151] In the lithium-ion secondary battery electrode (negative electrode or positive electrode for lithium-ion secondary battery) of the present invention, the content of the undercoat layer constituent material (negative electrode undercoat layer constituent material or positive electrode undercoat layer constituent material), excluding conductive additives, in the undercoat layer is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and even more preferably 40 to 60% by mass, from the viewpoint of not inhibiting lithium ion movement, even if the electrode constituent material such as binders, thickeners, and dispersants in the electrode active material layer is either not present or is in a very small amount, making it easier to homogenize the reaction within the battery, making it easier to extend the battery life, making it easier to improve the strength of the battery, and making it easier for cracks to occur due to pressing during electrode manufacturing even when high load pressure is applied locally. When multiple undercoat layer constituent materials (negative electrode undercoat layer constituent material or positive electrode undercoat layer constituent material), excluding conductive additives, are used, it is preferable to adjust the total amount so that it falls within the above range. Furthermore, in the undercoat layer, the total amount of the conductive additive and the undercoat layer constituent materials excluding the conductive additive (total amount of the undercoat layer) is 100% by mass.
[0152] [1-3-3] Undercoat layer In the lithium-ion secondary battery electrode (negative electrode or positive electrode) of the present invention, the thickness of the undercoat layer is preferably above a certain level from the viewpoint of improving the strength of the battery and preventing cracks from occurring due to pressing during electrode manufacturing even when high load pressure is applied locally. On the other hand, even if the electrode constituent materials such as binders, thickeners, and dispersants in the electrode active material layer are not present or are present in very small amounts, it is preferable to make the undercoat layer as thin as possible from the viewpoint of making it easier to homogenize the reaction in the battery and extend the battery life, as it does not easily hinder the movement of lithium ions. For this reason, the thickness of the undercoat layer in the lithium-ion secondary battery electrode (negative electrode or positive electrode) of the present invention is preferably 0.1 to 10.0 μm, more preferably 0.5 to 7.0 μm, and even more preferably 1.0 to 5.0 μm. While some undercoat layers are composed of materials that inhibit lithium ion movement, the above thickness makes it easier to improve the strength of the battery, reduces the likelihood of cracks occurring due to pressing during electrode manufacturing, prevents the undercoat layer from separating from the electrode active material layer, and minimizes the impact on reaction uniformity, thus facilitating the homogenization of the reaction.
[0153] 2. Method for manufacturing electrodes for lithium-ion secondary batteries The method for manufacturing the electrode active material layer and the electrode for a lithium-ion secondary battery of the present invention is not particularly limited, but for example, when forming an undercoat layer, (1) A step of applying an undercoat layer forming composition onto an electrode current collector to form an undercoat layer. (2) A step of forming the electrode active material layer on the undercoat layer formed on the electrode current collector using an electrode active material layer forming composition. Equipped with, The electrode active material layer forming composition contains at least an electrode active material and carbon nanotubes, The electrode active material comprises an electrode active material (1) with an average particle diameter of less than 8.0 μm and an electrode active material (2) with an average particle diameter of greater than 8.0 μm. Assuming the total amount of the electrode active material layer for the lithium-ion secondary battery is 100% by mass, The total carbon nanotube content is 0.01 to 1.4% by mass, and With the total amount of the electrode active material being 100% by mass, the content of electrode active material (1) is 1 to 45% by mass, and the content of electrode active material (2) is 55 to 99% by mass.
[0154] If an undercoat layer is not formed, the electrode active material layer for lithium-ion secondary batteries and the electrode for lithium-ion secondary batteries of the present invention can be manufactured by forming the electrode active material layer on the electrode current collector using the above-mentioned electrode active material layer forming composition.
[0155] (2-1) Process (1) In step (1), the electrode current collector and the undercoat layer can be those described above. The undercoat layer forming composition is a composition capable of forming the undercoat layer described above, and can contain the same components as the undercoat layer described above. The content of each component in the undercoat layer forming composition can also be the same as that of the undercoat layer described above.
[0156] In a composition for forming an undercoat layer, when mixing at least carbon nanotubes, optionally conductive additives other than carbon nanotubes, and optionally undercoat layer constituent materials other than conductive additives to form an undercoat layer paste composition, it is also possible to make it into a paste by including one or more organic solvents such as water, alcohol (methanol, ethanol, n-propyl alcohol, isopropyl alcohol, etc.), acetone, N-methylpyrrolidone, dimethyl sulfoxide, and dimethylformamide. In this case, the content of each component is a value with the total amount of carbon nanotubes, optionally conductive additives other than carbon nanotubes, and optionally undercoat layer constituent materials other than conductive additives, i.e., the total amount of solids, as 100% by mass.
[0157] The method for producing the undercoat layer-forming composition is not particularly limited. For example, the undercoat layer-forming composition can be produced by mixing the above-mentioned components by a conventional method.
[0158] The undercoat layer can be manufactured by forming the above-described undercoat layer-forming composition into layers. For example, if the undercoat layer-forming composition is an undercoat layer-forming paste composition, the paste composition can be applied to the electrode current collector by a conventional method, dried by a conventional method as needed, and formed into layers.
[0159] (2-2) Process (2) In step (1), the electrode current collector, undercoat layer, and electrode active material layer can be those described above. The electrode active material layer forming composition is a composition capable of forming the electrode active material layer described above, and can contain the same components as the electrode active material layer described above. The content of each component in the electrode active material layer forming composition can also be the same as that of the electrode active material layer described above.
[0160] In a composition for forming an electrode active material layer, if a paste composition for forming an electrode active material layer is made by mixing at least an electrode active material, carbon nanotubes, a conductive additive other than carbon nanotubes if necessary, and electrode constituent materials excluding the electrode active material, carbon nanotubes, and conductive additives other than carbon nanotubes if necessary, it is also possible to make it into a paste by including one or more organic solvents such as water, alcohol (methanol, ethanol, n-propyl alcohol, isopropyl alcohol, etc.), acetone, N-methylpyrrolidone, dimethyl sulfoxide, and dimethylformamide. In this case, the content of each component is a value with the total amount of the electrode active material, carbon nanotubes, a conductive additive other than carbon nanotubes if necessary, and electrode constituent materials excluding the electrode active material, carbon nanotubes, and conductive additives other than carbon nanotubes if necessary, i.e., the total amount of solids is taken as 100% by mass.
[0161] The method for producing the electrode active material layer formation composition is not particularly limited. For example, the electrode active material layer formation composition can be produced by mixing the above-mentioned components by a conventional method.
[0162] The electrode active material layer can be manufactured by forming the above-described electrode active material layer forming composition into layers. For example, if the electrode active material layer forming composition is an electrode active material layer forming paste composition, the layer can be formed on the undercoat layer obtained in step (1) by a conventional method using the paste composition. Specifically, the electrode active material layer forming paste composition can be applied or transferred onto the undercoat layer obtained in step (1), and dried by a conventional method as needed to form layers.
[0163] 3. Lithium-ion rechargeable batteries The lithium-ion secondary battery of the present invention is equipped with the lithium-ion secondary battery electrode of the present invention (negative electrode or positive electrode for lithium-ion secondary battery) described above. When the lithium-ion secondary battery electrode of the present invention is used as the negative electrode, the positive electrode can be either the lithium-ion secondary battery electrode of the present invention or a positive electrode applied to a known lithium-ion secondary battery. Furthermore, when the lithium-ion secondary battery electrode of the present invention is used as the positive electrode, the negative electrode can be either the lithium-ion secondary battery electrode of the present invention or a negative electrode applied to a known lithium-ion secondary battery. In addition, the lithium-ion secondary battery of the present invention may also be equipped with an electrolyte applied to a known lithium-ion secondary battery and a container for housing these electrode components.
[0164] When using a known negative electrode applicable to lithium-ion secondary batteries, there are no particular restrictions on the negative electrode, and any well-known negative electrode can be used. An example of a well-known negative electrode is shown below.
[0165] As the negative electrode current collector constituting the negative electrode, it is preferably made of a material that is electrochemically stable at the potential of use and has high electron conductivity, such as copper, stainless steel, nickel, carbon materials and the like. This negative electrode current collector can be a member in the form of, for example, a foil, a mesh, or the like.
[0166] Further, as the negative electrode active material constituting the negative electrode, a material capable of occluding and releasing lithium ions is usually used. For example, carbon materials such as natural graphite, artificial graphite, and amorphous carbon; metal materials capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Si alloys, Sn alloys, Al alloys and the like; SiO x (0<x<2), SnO x (0<x<2), Si, Li₂TiO₃, vanadium oxides and other metal oxides capable of occluding and releasing lithium ions; composite materials containing a metal material and a carbon material such as a Si-C composite, a Sn-C composite, and the like. These negative electrode active materials may be used alone, or two or more thereof may be used in combination. From the viewpoint of particularly suppressing the volume change of the electrode active material (negative electrode active material) during charge and discharge and easily improving the charge-discharge cycle characteristics, a silicon-free material, that is, a carbon material; a silicon-free metal material such as Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Sn alloys, Al alloys and other metal materials capable of alloying with lithium; SnO x (0<x<2), Si, Li₂TiO₃, vanadium oxides and other silicon-free metal oxides capable of occluding and releasing lithium ions; silicon-free composite materials containing a metal material and a carbon material such as a Sn-C composite and the like can also be employed. Above all, when a conductive material such as a carbon material is used as the negative electrode active material, the negative electrode active material also functions as a conductive aid, making it particularly easy to reduce the content of substances that inhibit the movement of lithium ions.
[0167] As for the electrode active material (negative electrode active material) described above, from the viewpoint of particularly suppressing the volume change of the electrode active material (negative electrode active material) during charging and discharging, making it easier to suppress the decrease in capacity due to volume change, and particularly improving the charge-discharge cycle characteristics, it is preferable that the volume change of the electrode active material (negative electrode active material) during charging and discharging is 150% or less, preferably 120% or less. The smaller the volume change, the better, and no lower limit is set, but if a lower limit were set, it would be 0%. This volume change value is set to 0% when there is no volume change at all, and indicates the extent to which the electrode active material (negative electrode active material) expands when fully charged compared to when fully discharged, as shown by the following formula: (Volume when fully charged) - (Volume when fully discharged) / (Volume when fully discharged) × 100 It is calculated by [method].
[0168] Other than the negative electrode active material that constitutes the negative electrode, the same conductive additives other than carbon nanotubes and other negative electrode materials as those used in the lithium-ion secondary battery electrode of the present invention described above can be used, and their content can be in the amounts commonly used.
[0169] When using a known positive electrode applicable to lithium-ion secondary batteries, any positive electrode capable of supplying lithium ions to the negative electrode is acceptable, and any well-known positive electrode can be used. An example of a well-known positive electrode is shown below.
[0170] Examples of materials that can be used as the positive electrode current collector include aluminum, stainless steel, and carbon materials, which are electrochemically stable at the potential being used and have high electronic conductivity.
[0171] Furthermore, as the positive electrode active material constituting the positive electrode, a material capable of intercalating and releasing lithium ions is usually used. Examples include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal oxides having a spinel type crystal structure, polyanionic compounds, chalcogen compounds, sulfur, etc. As an example of a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, Li[Li x1 Ni γ1 Mn β1 Co (1-x1-γ1-β1) ]O2(0≦x1<0.5, 0≦γ1≦1, 0≦β1≦1, 0≦γ1+β1≦1), Li[Li x2 Ni γ2 Co β2 Al (1-x2-γ2-β2) Examples include ]O2 (0≦x2<0.5, 0≦γ2≦1, 0≦β2≦1, 0≦γ2+β2≦1), etc. As a lithium transition metal oxide having a spinel-type crystal structure, Li x3 Mn2O4 (0.9 ≤ x 3 < 1.5), Li x4 Ni γ4 Mn (2-γ4) Examples include O4 (0.9 ≤ x4 < 1.5, 0 ≤ γ4 ≤ 2). Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Some atoms or polyanions in these materials may be substituted with atoms or anion species of other elements. These positive electrode active materials can be used individually or in combination of two or more. Among these, the lithium transition metal composite oxides are preferred as positive electrode active materials from the viewpoint of increasing energy density.
[0172] Other than the positive electrode active material that constitutes the positive electrode, the same materials as those used in the electrode for lithium-ion secondary batteries of the present invention, excluding the electrode active material and carbon nanotubes, can be used as positive electrode constituent materials, and their content can also be the same as that used in the electrode for lithium-ion secondary batteries of the present invention, excluding the electrode active material and carbon nanotubes.
[0173] Furthermore, the electrolyte is preferably an electrolyte obtained by dissolving a salt in an aprotic organic solvent, and is placed between the positive electrode and the negative electrode. It is preferable that the electrolyte is impregnated and held in a separator made of, for example, a nonwoven fabric to prevent short circuits between the positive and negative electrodes.
[0174] Examples of aprotic organic solvents that constitute the electrolyte mentioned above include esters such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, γ-butyrolactone, methyl formate, and methyl acetate; furans such as tetrahydrofuran and 2-methyltetrahydrofuran; ethers such as dioxolane, diethyl ether, dimethoxyethane, diethoxyethane, and methoxyethoxyethane; dimethyl sulfoxide; sulforanes such as sulfolane and methylsulfolane; and acetonitrile. These aprotic organic solvents may be used individually or in combination of two or more.
[0175] On the other hand, examples of lithium salts that dissolve in such aprotic organic solvents include lithium perchlorate, lithium borofluoride, lithium hexafluoride phosphate, lithium hexafluoride arsenate, lithium trifluoromethanesulfonate, lithium halides, lithium aluminate chloride, and lithium bis(fluorosulfonyl)imide. These salts may be used individually or in combination of two or more.
[0176] Because the lithium-ion secondary battery of the present invention uses the lithium-ion secondary battery electrode of the present invention (negative electrode or positive electrode for lithium-ion secondary battery) for the negative electrode and / or positive electrode, it has sufficient strength to maintain the shape of the electrode, does not crack due to pressing during electrode manufacturing, does not delaminate between the undercoat layer and the electrode active material layer, and does not easily hinder the movement of lithium ions, thus homogenizing the reaction within the battery and extending the battery life. For this reason, this lithium-ion secondary battery is expected to be deployed in the market in the future and can be effectively used in electric vehicle applications for car sharing, particularly in AIEV (Artificial Intelligence Electric Vehicle) applications, where further extended lifespan will be required. [Examples]
[0177] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0178] [Examples 1-3 and Comparative Examples 1-3: Positive electrodes for lithium-ion secondary batteries] Comparative Example 1 Large particle size LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 98.5% by mass of O2 (large particle size NCM; average particle diameter 15 μm), 0.5% by mass of single-walled carbon nanotubes (bundled single-walled CNT aggregates; average outer diameter 2 nm, average length > 5 μm, G / D: 80~150 per single-walled CNT), 1.0% by mass of acetylene black (AB; average particle diameter 30 nm) as a conductive additive other than carbon nanotubes, and an appropriate amount of N-methylpyrrolidone were added and kneaded to form a slurry. An undercoat layer was placed on top of aluminum foil (thickness 15 μm) which served as the positive electrode current collector. The undercoat layer consisted of 50% by mass of carbon black (average particle diameter 30 nm), 50% by mass of carboxymethylcellulose (CMC), and a thickness of 1 μm. After drying with a doctor blade, the mass per unit area of the positive electrode active material layer was 19.0 mg / cm². 2The coating is applied in this manner, and then pressed using a roll press at a linear pressure of 1.5 kN / cm². 2 The density is 3.0 g / cm³. 3 The material was pressed in this manner. Afterwards, it was dried in a vacuum atmosphere at 170°C, and the positive electrode was obtained after pressing.
[0179] Comparative Example 2 Next, as the positive electrode active material, large particle size LiNi 0.6 Co 0.2 Mn 0.2 98.5% by mass of O2 (large particle size NCM; average particle diameter 10 μm), 0.5% by mass of single-walled carbon nanotubes (bundled single-walled CNT aggregates; average outer diameter 2 nm, average length > 5 μm per single-walled CNT, G / D: 80~150), 1.0% by mass of acetylene black (AB; average particle diameter 30 nm) as a conductive additive other than carbon nanotubes, and an appropriate amount of N-methylpyrrolidone were added and kneaded to form a slurry. An undercoat layer was placed on top of aluminum foil (thickness 15 μm) which served as the positive electrode current collector. The undercoat layer consisted of 50% by mass of carbon black (average particle diameter 30 nm), 50% by mass of carboxymethylcellulose (CMC), and a thickness of 1 μm. After drying with a doctor blade, the mass per unit area of the positive electrode active material layer was 19.0 mg / cm². 2 The coating is applied in this manner, and then pressed using a roll press at a linear pressure of 1.5 kN / cm². 2 The density is 3.0 g / cm³. 3 The material was pressed in this manner. Afterwards, it was dried in a vacuum atmosphere at 170°C, and the positive electrode was obtained after pressing.
[0180] Comparative Example 3 Next, as the positive electrode active material, small particle size LiNi 0.6 Co 0.2 Mn 0.298.5% by mass of O2 (small particle size NCM; average particle diameter 5 μm), 0.5% by mass of single-walled carbon nanotubes (bundled single-walled CNT aggregates; average outer diameter 2 nm, average length > 5 μm, G / D: 80~150 per single-walled CNT), 1.0% by mass of acetylene black (AB; average particle diameter 30 nm) as a conductive additive other than carbon nanotubes, and an appropriate amount of N-methylpyrrolidone were added and kneaded to form a slurry. An undercoat layer was placed on top of aluminum foil (thickness 15 μm) which served as the positive electrode current collector. The undercoat layer consisted of 50% by mass of carbon black (average particle diameter 30 nm), 50% by mass of carboxymethylcellulose (CMC), and a thickness of 1 μm. After drying with a doctor blade, the mass per unit area of the positive electrode active material layer was 19.0 mg / cm². 2 Apply in this manner, and then roll press to 3.0 g / cm 3 We aimed for this and pressed it, but it was 5kN / cm 3 Even with the line pressure increased to this level, it remains at 2.88 g / cm². 3 It only reached this point. Afterwards, it was dried in a vacuum atmosphere at 170°C, and the positive electrode was obtained after pressing.
[0181] Example 1 Next, as the positive electrode active material, large particle size LiNi 0.6 Co 0.2 Mn 0.2 O2 (large particle size NCM; average particle diameter 10 μm) and small particle size LiNi 0.6 Co 0.2 Mn 0.2A slurry was prepared by mixing 98.5% by mass of O2 (small particle size NCM; average particle diameter 5 μm) (large particle size NCM:small particle size NCM = 70:30), 0.5% by mass of single-walled carbon nanotubes (bundled single-walled CNT aggregates; average outer diameter 2 nm, average length > 5 μm per single-walled CNT, G / D: 80~150), 1.0% by mass of acetylene black (AB; average particle size 30 nm) as a conductive additive other than carbon nanotubes, and an appropriate amount of N-methylpyrrolidone. This slurry was then applied to an undercoat layer on an aluminum foil (thickness 15 μm) which served as the positive electrode current collector. The undercoat layer consisted of 50% by mass of carbon black (average particle size 30 nm), 50% by mass of carboxymethylcellulose (CMC), and a thickness of 1 μm. After drying with a doctor blade, the mass per unit area of the positive electrode active material layer was 19.0 mg / cm². 2 The coating is applied in this manner, and then pressed using a roll press at a linear pressure of 1.0 kN / cm². 2 The density is 3.0 g / cm³. 3 The material was pressed in this manner. Afterwards, it was dried in a vacuum atmosphere at 170°C, and the positive electrode was obtained after pressing.
[0182] Example 2 Next, as the positive electrode active material, large particle size LiNi 0.6 Co 0.2 Mn 0.2 O2 (large particle size NCM; average particle diameter 10 μm) and small particle size LiNi 0.6 Co 0.2 Mn 0.2A slurry was prepared by mixing 98.5% by mass of O2 (small particle size NCM; average particle diameter 5 μm) (large particle size NCM:small particle size NCM = 65:35), 0.5% by mass of single-walled carbon nanotubes (bundled single-walled CNT aggregates; average outer diameter 2 nm, average length > 5 μm per single-walled CNT, G / D: 80~150), 1.0% by mass of acetylene black (AB; average particle size 30 nm) as a conductive additive other than carbon nanotubes, and an appropriate amount of N-methylpyrrolidone. This slurry was then applied to an undercoat layer on an aluminum foil (thickness 15 μm) which served as the positive electrode current collector. The undercoat layer consisted of 50% by mass of carbon black (average particle size 30 nm), 50% by mass of carboxymethylcellulose (CMC), and a thickness of 1 μm. After drying with a doctor blade, the mass per unit area of the positive electrode active material layer was 19.0 mg / cm². 2 The coating is applied in this manner, and then pressed using a roll press at a linear pressure of 1.0 kN / cm². 2 The density is 3.0 g / cm³. 3 The material was pressed in this manner. Afterwards, it was dried in a vacuum atmosphere at 170°C, and the positive electrode was obtained after pressing.
[0183] Example 3 Next, as the positive electrode active material, large particle size LiNi 0.6 Co 0.2 Mn 0.2 O2 (large particle size NCM; average particle diameter 10 μm) and small particle size LiNi 0.6 Co 0.2 Mn 0.2A slurry was prepared by mixing 98.5% by mass of O2 (small particle size NCM; average particle diameter 5 μm) (large particle size NCM:small particle size NCM = 60:40), 0.5% by mass of single-walled carbon nanotubes (bundled single-walled CNT aggregates; average outer diameter 2 nm, average length > 5 μm per single-walled CNT, G / D: 80~150), 1.0% by mass of acetylene black (AB; average particle size 30 nm) as a conductive additive other than carbon nanotubes, and an appropriate amount of N-methylpyrrolidone. This slurry was then applied to an undercoat layer on an aluminum foil (thickness 15 μm) which served as the positive electrode current collector. The undercoat layer consisted of 50% by mass of carbon black (average particle size 30 nm), 50% by mass of carboxymethylcellulose (CMC), and a thickness of 1 μm. After drying with a doctor blade, the mass per unit area of the positive electrode active material layer was 19.0 mg / cm². 2 The coating is applied in this manner, and then pressed using a roll press at a linear pressure of 1.0 kN / cm². 2 The density is 3.0 g / cm³. 3 The material was pressed in this manner. Afterwards, it was dried in a vacuum atmosphere at 170°C, and the positive electrode was obtained after pressing.
[0184] Test Example 1: Press Resistance Test The press resistance of the pre-press positive electrodes obtained in Examples 1-3 and Comparative Examples 1-3 was evaluated by punching them out to 2cm x 5cm, roll pressing them under a linear pressure of 2kN / cm, and observing the surface condition of the electrodes.
[0185] Furthermore, ○: No lifting at all in the positive electrode. △: Lifting occurs in a very small area at the positive electrode. ×: Cracks may occur in the positive electrode active material layer, or the positive electrode active material layer may peel off from the positive electrode current collector. This was the evaluation. The results are shown in Table 1.
[0186] Similarly, the pre-press positive electrodes obtained in Examples 1-3 and Comparative Examples 1-3 were punched out to 2cm x 5cm and roll-pressed with a linear pressure varying from 0 to 5kN / cm, resulting in an electrode density of 19.0 mg / cm³ per unit area of the positive electrode active material layer.2 The thickness was calculated by dividing the thickness of the positive electrode composite layer (including the positive electrode current collector, undercoat layer, and positive electrode active material layer, measured with a micrometer) by the thickness of the positive electrode composite layer, which is obtained by subtracting the thickness of the positive electrode current collector and undercoat layer (16 μm). The results are shown in Figure 2.
[0187] Test Example 2: Powder Compression Density Inner diameter 0.35cm (area 0.096cm 2 0.3g of the positive electrode active material used in Examples 1-3 and Comparative Examples 2-3 was packed into a glass tube, a copper rod with an outer diameter of 0.35cm was inserted, and a pressure of 75kgf / cm² was applied. 2 By applying pressure and measuring the displacement of the copper rod with a micrometer, the thickness of the compressed positive electrode active material is measured, and the thickness of the compressed positive electrode active material and the area corresponding to the inner diameter of the glass tube (0.096 cm²) are measured. 2 The volume of the compressed positive electrode active material was calculated, and the compression density was measured by dividing the mass of the filled positive electrode active material (0.3g) by the volume of the compressed positive electrode active material. The results are shown in Table 1 and Figure 3.
[0188] Manufacturing example: Manufacturing of lithium-ion rechargeable batteries As the positive electrode, the pre-pressed positive electrodes obtained in Example 1 and Comparative Examples 1-3 were used, with a positive electrode active material layer density of 3.0 g / cm³. 3 The cathode was manufactured by roll pressing in this manner and then drying under reduced pressure at 170°C.
[0189] Next, 99.17% by mass of natural graphite (graphite; average particle size 4 μm) as the negative electrode active material, 0.33% by mass of single-walled carbon nanotubes (bundled single-walled CNT aggregates; average outer diameter 2 nm, average length > 5 μm, G / D: 80~150 per single-walled CNT), 0.5% by mass of carboxymethylcellulose (CMC) as other negative electrode constituent materials, and an appropriate amount of water are added and kneaded to form a slurry. This slurry is then applied to a copper foil (thickness 8 μm) which serves as the negative electrode current collector, with an undercoat layer consisting of 50% by mass of carbon black (average particle size 30 nm), 50% by mass of binder, and a thickness of 1 μm. The weight per unit area of the negative electrode active material layer after drying with a ConnReverse coater is 10.0 mg / cm². 2 The material is applied in such a manner, and after drying at 60°C, the density of the negative electrode active material layer is 1.3 g / cm³. 3 The material was roll-pressed in this manner, dried under reduced pressure at 120°C, and a negative electrode was obtained.
[0190] The electrolyte used consisted of a mixture of ethylene carbonate (EC) and methyl ethyl carbonate (MEC) as solvents in a volume ratio of 3:7, and 1 mol / L lithium hexafluoride phosphate (LiPF6) as the salt. This electrolyte was impregnated into a polyethylene porous film, which served as the separator.
[0191] A lithium-ion secondary battery was fabricated using the above-described positive electrode, negative electrode, electrolyte, and separator. The opposing surface area of the positive and negative electrodes of the fabricated lithium-ion secondary battery was 2.8 cm². 2 That's what I decided.
[0192] Test Example 3: Lifetime Characteristics Charge-discharge cycle tests were performed at 50°C on the lithium-ion secondary batteries of Example 1 and Comparative Examples 1-3. The charge-discharge conditions were as follows: constant current constant voltage (CCCV) charging was performed at a charge rate of 0.5C until the current value reached 0.05C up to an upper voltage limit of 4.08V, followed by a 10-minute pause, and then discharge at a discharge rate of 0.5C up to a lower voltage limit of 2.7V, followed by another 10-minute pause. These charge-discharge processes constituted one cycle, and the charge-discharge cycle test was performed for 150 cycles. The discharge capacity after 150 cycles is shown in Table 1, with the discharge capacity after the first cycle set to 100%.
[0193] [Table 1]
Claims
1. It contains at least an electrode active material and carbon nanotubes, The electrode active material contains an electrode active material (1) with an average particle diameter of less than 8.0 μm and an electrode active material (2) with an average particle diameter of greater than 8.0 μm. Assuming the total amount of the electrode active material layer for the lithium-ion secondary battery is 100% by mass, The total carbon nanotube content is 0.01 to 1.4% by mass, and An electrode active material layer for a lithium-ion secondary battery, wherein, with the total amount of the electrode active material being 100% by mass, the content of electrode active material (1) is 1 to 45% by mass, and the content of electrode active material (2) is 55 to 99% by mass.
2. Assuming the total amount of the electrode active material layer for the lithium-ion secondary battery is 100% by mass, The content of the electrode active material is 96.0 to 99.9% by mass. The content of conductive additives other than carbon nanotubes is 0 to 3.5% by mass. The electrode active material layer for a lithium-ion secondary battery according to claim 1, wherein the content of the electrode constituent materials, excluding the electrode active material, the carbon nanotubes, and conductive additives other than the carbon nanotubes, is 0 to 2.0% by mass.
3. Assuming the total amount of the electrode active material layer is 100% by mass, The content of the electrode active material is 96.0 to 99.9% by mass. The content of conductive additives other than carbon nanotubes is 0 to 3.5% by mass. It does not contain electrode constituent materials other than the electrode active material, the carbon nanotube, and the conductive additive other than the carbon nanotube, This is the positive electrode for lithium-ion secondary batteries. The electrode active material layer for a lithium-ion secondary battery according to claim 2.
4. Assuming the total amount of the electrode active material layer is 100% by mass, The content of the electrode active material is 96.6 to 99.9% by mass. The content of electrode constituent materials other than the electrode active material and the carbon nanotubes is 0 to 2.0% by mass, and The negative electrode for lithium-ion secondary batteries, The electrode active material layer for a lithium-ion secondary battery according to claim 2.
5. Assuming the total amount of the electrode active material layer is 100% by mass, The content of the electrode active material is 97.4 to 99.9% by mass. The content of electrode constituent materials other than the electrode active material and the carbon nanotubes is 0 to 1.2% by mass. The electrode active material layer for a lithium-ion secondary battery according to claim 2.
6. The electrode active material layer for a lithium-ion secondary battery according to claim 5, which is a negative electrode active material layer for a lithium-ion secondary battery.
7. The electrode active material layer for a lithium-ion secondary battery according to claim 1, wherein the electrode active material is a material capable of intercalating and releasing lithium ions.
8. The electrode active material layer for a lithium-ion secondary battery according to claim 1, which is for a lithium-ion secondary battery used in an electric vehicle for car sharing.
9. An electrode for a lithium-ion secondary battery, comprising an electrode current collector, an undercoat layer, and an electrode active material layer for a lithium-ion secondary battery according to any one of claims 1 to 8.
10. The electrode for a lithium-ion secondary battery according to claim 9, wherein the undercoat layer contains at least a conductive additive and the undercoat layer constituent material excluding the conductive additive.
11. The electrode for a lithium-ion secondary battery according to claim 10, wherein, with a total amount of the undercoat layer being 100% by mass, the content of the conductive additive is 20 to 80% by mass, and the content of the undercoat layer constituent materials excluding the conductive additive is 20 to 80% by mass.
12. The electrode for a lithium-ion secondary battery according to claim 9, wherein the thickness of the undercoat layer is 0.1 to 10.0 μm.
13. An electrode for a lithium-ion secondary battery according to claim 9, which is for a lithium-ion secondary battery used in an electric vehicle for car sharing.
14. A lithium-ion secondary battery comprising the lithium-ion secondary battery electrode described in claim 9.
15. A lithium-ion secondary battery according to claim 14, used in an electric vehicle for car sharing.
Citation Information
Patent Citations
Composition for forming electrode active material layer for lithium ion secondary batteries
WO2023090443A1